Hydrogenated conjugated diene polymer, hydrogenated conjugated diene polymer composition and rubber composition, and method for producing hydrogenated conjugated diene polymer
A hydrogenated conjugated diene polymer with controlled branching and hydrogenation addresses dispersibility and processability issues, achieving superior breaking strength, elongation, and low hysteresis loss in rubber compositions.
Patent Information
- Application Number
- CN202180022272.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-06
- Filing Date
- 2021-04-05
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-04-05
AI Technical Summary
Existing rubber compositions containing silica face issues with dispersibility due to hydrophilic surfaces, leading to increased viscosity and difficulty in kneading, and insufficient balance between wear resistance and low hysteresis loss, along with potential cold flow and handling problems.
A hydrogenated conjugated diene polymer with a specific branching degree (Bn) and hydrogenation rate, combined with a star-shaped structure and alkoxysilyl or halosilyl groups, enhances dispersibility and processability while maintaining excellent breaking strength and elongation.
The polymer suppresses cold flow, improves processability, and achieves superior breaking strength and elongation, balancing wear resistance and low hysteresis loss, with enhanced wet skid resistance.
Smart Images

Figure BDA0003851819470000031 
Figure BDA0003851819470000041 
Figure BDA0003851819470000051
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrogenated conjugated diene polymer, a hydrogenated conjugated diene polymer composition and a rubber composition, and a method for producing the hydrogenated conjugated diene polymer. Background Art
[0002] In recent years, in consideration of environmental impact, there is an increasing demand for lower fuel consumption in automobiles. In particular, in automobile tires, there is a demand for improved fuel consumption in materials used in the tread portion that comes into direct contact with the ground.
[0003] In recent years, there has been a demand for the development of materials having low rolling resistance, that is, low hysteresis loss.
[0004] At the same time, due to the trend of lightweight tires, in order to make the tires lighter, it is particularly necessary to reduce the thickness of the tread portion that contacts the road surface and has a high material ratio, and rubber materials with excellent breaking strength, breaking elongation, and wear resistance are needed more than before.
[0005] Furthermore, in order to reduce energy loss caused by the tire during driving, the rubber material used for the tire tread needs to have low rolling resistance, that is, low hysteresis loss.
[0006] On the other hand, from the viewpoint of safety, it is required to have excellent handling stability and wet skid resistance and sufficient breaking strength for practical use.
[0007] Examples of rubber materials that meet the above requirements include rubber compositions containing a rubber-like polymer and a reinforcing filler such as carbon black or silica.
[0008] When a rubber composition containing silica is used, it is possible to improve the balance between low hysteresis loss (an indicator of low fuel consumption) and wet skid resistance. In addition, by introducing a functional group having affinity or reactivity with silica into the molecular terminal of a rubber-like polymer with high mobility, the dispersibility of silica in the rubber material can be improved, and the mobility of the molecular terminal of the rubber-like polymer can be reduced by bonding with silica particles, thereby reducing hysteresis loss.
[0009] On the other hand, as a method for improving breaking strength, breaking elongation, and abrasion resistance, a method of increasing the molecular weight can be cited. However, if the molecular weight is increased, the processability of the rubber-like polymer when kneading with the reinforcing filler tends to deteriorate.
[0010] In view of such circumstances, attempts have been made to introduce a branched structure into the rubber-like polymer to increase the molecular weight and to introduce a hydrogenation technique in order to improve the breaking strength, breaking elongation, and abrasion resistance without impairing the processability.
[0011] For example, Patent Documents 1 to 3 propose compositions of a modified conjugated diene polymer obtained by reacting an amino group-containing alkoxysilane with an active terminal of a conjugated diene polymer and silicon oxide.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application Publication No. 2005-290355
[0015] Patent Document 2: Japanese Patent Application Laid-Open No. 11-189616
[0016] Patent Document 3: Japanese Patent Application Publication No. 2003-171418 Summary of the invention
[0017] Problems to be solved by the invention
[0018] However, compared to carbon black having a hydrophobic surface, silicon oxide has a hydrophilic surface, and therefore, due to its low affinity with the conjugated diene polymer, silicon oxide has a disadvantage that its dispersibility in the composition is inferior to that of carbon black. Therefore, in the composition containing silicon oxide, in order to provide bonding between silicon oxide and the conjugated diene polymer and improve the dispersibility in the composition, it is necessary to separately contain a silane modifier or the like.
[0019] In addition, when a functional group highly reactive with silicon oxide is introduced into the molecular terminal of a conjugated diene polymer, the following tendency of deterioration in processability is observed: during the kneading step, the reaction with silicon oxide particles occurs, and kneading becomes difficult due to increased viscosity of the composition; or when a sheet is formed after kneading, surface roughness easily occurs or the sheet is easily broken.
[0020] Furthermore, when such a composition is made into a sulfide, particularly when it is made into a sulfide containing an inorganic filler such as silicon oxide, the balance between wear resistance and low hysteresis loss and wet skid resistance is insufficient.
[0021] Furthermore, even when the hydrogenation technology is introduced, the viscosity of the conjugated diene polymer increases due to hydrogenation. Therefore, the viscosity of the composition increases significantly due to the molecular weight, branched structure, and modification of the hydrogenated conjugated diene polymer, and the following tendency of deterioration in processability is observed: kneading becomes difficult; or when the sheet is formed after kneading, the surface is easily roughened or the sheet is easily broken.
[0022] Furthermore, if the polymer chains in the conjugated diene polymer and the hydrogenated conjugated diene polymer are less entangled, a phenomenon called cold flow occurs when the rubber mass flows and deforms when stored at room temperature, and the handling property during use deteriorates.
[0023] Therefore, an object of the present invention is to provide a hydrogenated conjugated diene polymer, a hydrogenated conjugated diene polymer composition and a rubber composition which suppress cold flow of a rubber compact, have extremely excellent processability when produced as a vulcanizate, and have excellent breaking strength, breaking elongation and fracture characteristics after being produced as a vulcanizate.
[0024] Means for solving problems
[0025] The present inventors have conducted intensive studies and discussions to solve the above-mentioned problems of the prior art. As a result, they have found that a hydrogenated conjugated diene polymer having a branching degree (Bn) and a hydrogenation rate within a specific range can suppress the cold flow of a rubber compact and has extremely excellent processability when made into a vulcanizate, and that the vulcanizate has excellent breaking strength, breaking elongation and fracture characteristics, thereby completing the present invention.
[0026] That is, the present invention relates to the following aspects. [1]
[0028] A hydrogenated conjugated diene polymer, wherein the degree of branching (Bn) measured by GPC-light scattering method with a viscosity detector is 2.5 or more, and the hydrogenation rate of the structural unit derived from the conjugated diene compound is 30% or more and less than 99%. [2]
[0030] The hydrogenated conjugated diene polymer according to [1], wherein the weight average molecular weight based on GPC is 210,000 or more and less than 3,000,000. [3]
[0032] The hydrogenated conjugated diene polymer as described in [1] or [2], wherein the following mathematical formula (S) is satisfied when the constituent ratios (mol %) of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3) and the structural unit represented by the following formula (4) are respectively a, b, c and d.
[0033] [Chemistry 1]
[0034]
[0035] Mathematical formula (S): 20≤(a+b) / (a+b+c+d)×100≤65 [4]
[0037] The hydrogenated conjugated diene polymer according to any one of [1] to [3], wherein the following mathematical formula (T) is satisfied when the constituent ratios (mol %) of the structural unit represented by the following formula (1) and the structural unit represented by the following formula (2) are represented by a and b, respectively.
[0038] [Chemistry 2]
[0039]
[0040] Mathematical formula (T): 90≤(a) / (a+b)×100≤100 [5]
[0042] The hydrogenated conjugated diene polymer according to any one of [1] to [4] contains 3% by mass or more and less than 60% by mass of an aromatic vinyl monomer. [6]
[0044] The hydrogenated conjugated diene polymer according to any one of [1] to [5], wherein the modification rate is 60% by mass or more. [7]
[0046] The hydrogenated conjugated diene polymer according to any one of [1] to [6], wherein the degree of branching (Bn) measured by GPC-light scattering method with a viscosity detector is 8.0 or more. [8]
[0048] The hydrogenated conjugated diene polymer according to any one of [1] to [7], wherein
[0049] The hydrogenated conjugated diene polymer has a star-shaped polymer structure with three or more branches.
[0050] A moiety derived from a vinyl monomer containing an alkoxysilyl group or a halosilyl group is present on at least one branch of the star-shaped structure,
[0051] The portion derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group has a further main chain branch structure. [9]
[0053] The hydrogenated conjugated diene polymer according to [8], wherein
[0054] The moiety derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group is a monomer unit based on a compound represented by the following formula (5) or (6),
[0055] and having a branching point of the polymer chain caused by a monomer unit based on a compound represented by the following formula (5) or (6),
[0056] At least one end of the hydrogenated conjugated diene polymer is coupled with a coupling agent.
[0057] [Chemistry 3]
[0058]
[0059] (In formula (5), R 1 The group represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and a part of the group may have a branched structure.
[0060] R 2 ~R 3 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure.
[0061] When there are multiple R 1 ~R 3 Each one is independent.
[0062] X 1 represents a halogen atom. When there are plural X 1 Each one is independent.
[0063] m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3. (m+n+l) represents 3.)
[0064] [Chemistry 4]
[0065]
[0066] (In formula (6), R 2 ~R 5 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure.
[0067] When there are multiple R 2 ~R 5 Each one is independent.
[0068] X 2 ~X 3 Each independently represents a halogen atom. When there are plural X 2 ~X 3 Each one is independent.
[0069] m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3. (m+n+l) represents 3. a represents an integer from 0 to 2, b represents an integer from 0 to 3, and c represents an integer from 0 to 3. (a+b+c) represents 3. )
[10]
[0071] The hydrogenated conjugated diene polymer according to [9], wherein the hydrogenated conjugated diene polymer has a monomer unit based on a compound represented by the above formula (5), wherein R 1 is a hydrogen atom, m=0.
[11]
[0073] The hydrogenated conjugated diene polymer according to [9], wherein the hydrogenated conjugated diene polymer has a monomer unit based on a compound represented by the above formula (6), wherein m=0 and b=0.
[12]
[0075] The hydrogenated conjugated diene polymer according to [9], wherein the hydrogenated conjugated diene polymer has a monomer unit based on a compound represented by the above formula (5), wherein R 1 It is a hydrogen atom, m=0, l=0, n=3.
[13]
[0077] The hydrogenated conjugated diene polymer as described in [9], wherein the hydrogenated conjugated diene polymer has a monomer unit based on the compound represented by the above formula (6), wherein m=0, l=0, n=3, a=0, b=0, and c=3.
[14]
[0079] The hydrogenated conjugated diene polymer according to any one of [1] to
[13] , wherein the component having a molecular weight of 300,000 or less (component LM) accounts for 20% to 80%.
[15]
[0081] The hydrogenated conjugated diene polymer according to any one of [1] to
[14] , wherein the hydrogenation rate is 50% to 75%.
[16]
[0083] A method for producing a hydrogenated conjugated diene polymer, comprising the following steps (A) and (E), and further comprising at least one of the following steps (B) and (D),
[0084] In the hydrogenated conjugated diene polymer obtained in step (E), the degree of branching (Bn) measured by GPC-light scattering method with a viscosity detector is 2.5 or more, and the hydrogenation rate of the structural unit derived from the conjugated diene compound is 30% or more and less than 99%;
[0085] Step (A): a step of polymerizing a conjugated diene compound alone or polymerizing a conjugated diene compound and an aromatic vinyl compound to obtain a conjugated diene polymer;
[0086] Step (B): a step of reacting a branching agent with a conjugated diene polymer terminal to obtain a conjugated diene polymer solution containing a branched conjugated diene polymer having an active terminal;
[0087] Step (D): a step of reacting a coupling agent with the terminal of a conjugated diene polymer;
[0088] Step (E): a step of subjecting the conjugated diene polymer to a hydrogenation reaction to obtain a hydrogenated conjugated diene polymer.
[17]
[0090] The method for producing a hydrogenated conjugated diene polymer according to
[16] , comprising the step (D).
[18]
[0092] A hydrogenated conjugated diene polymer composition comprising 100 parts by mass of the hydrogenated conjugated diene polymer described in any one of [1] to
[15] and 1 to 60 parts by mass of a rubber softener.
[19]
[0094] A rubber composition comprising a rubber component and 5.0 parts by mass or more and 150 parts by mass or less of a filler relative to 100 parts by mass of the rubber component,
[0095] The rubber component contains 10 parts by mass or more of the hydrogenated conjugated diene polymer described in any one of [1] to
[15] or the hydrogenated conjugated diene polymer composition described in
[18] , based on 100 parts by mass of the total amount of the rubber component.
[0096] Effects of the Invention
[0097] According to the present invention, a hydrogenated conjugated diene polymer can be obtained which can suppress the cold flow of a rubber compact, has extremely excellent processability when preparing a vulcanizate, and has particularly excellent breaking strength, breaking elongation and fracture characteristics after preparing a vulcanizate. DETAILED DESCRIPTION
[0098] A specific embodiment of the present invention (hereinafter referred to as “this embodiment”) will be described in detail below.
[0099] It should be noted that the following embodiments are examples for explaining the present invention, and the present invention is not limited to the following embodiments. The present invention can be implemented by appropriately modifying the present invention within the scope of the gist thereof.
[0100] [Hydrogenated conjugated diene polymer]
[0101] In the hydrogenated conjugated diene polymer of the present embodiment, the degree of branching (hereinafter also referred to as "Bn") obtained by the GPC (gel permeation chromatography)-light scattering method with a viscosity detector is 2.5 or more, and the hydrogenation rate of the structural unit derived from the conjugated diene compound (hereinafter also referred to as "hydrogenation rate") is 30% to 99%.
[0102] As described above, the hydrogenated conjugated diene polymer with limited hydrogenation ratio and branching degree (Bn) can suppress the cold flow of the rubber compact, has extremely excellent processability when made into a vulcanizate, and has excellent destructive properties such as breaking strength and breaking elongation after being made into a vulcanizate.
[0103] In the hydrogenated conjugated diene polymer of the present embodiment, the amount of 1,2-vinyl bonds and the amount of aromatic vinyl compounds in the conjugated diene bond units are arbitrarily adjusted on the basis of limiting the hydrogenation rate and the degree of branching (Bn), thereby making it possible to arbitrarily adjust the glass transition temperature (hereinafter also referred to as "Tg") of the hydrogenated conjugated diene polymer while achieving extremely excellent processability when preparing a sulfide and improving the fracture properties such as breaking strength and breaking elongation after preparing the sulfide.
[0104] For example, by setting the 1,2-vinyl bond content and the aromatic vinyl compound content in the conjugated diene bond unit to be low, the Tg of the conjugated diene polymer can be lowered, and there is a tendency to obtain a rubber composition having improved wear resistance and breaking strength after being made into a vulcanizate, and further excellent low hysteresis loss properties.
[0105] Furthermore, by increasing the 1,2-vinyl bond content and the aromatic vinyl compound content in the conjugated diene bond units, the Tg of the conjugated diene polymer can be increased, and the processability when preparing a vulcanizate can be improved, and a rubber composition having excellent wet skid resistance tends to be obtained.
[0106] (Conjugated diene compound)
[0107] The hydrogenated conjugated diene polymer of the present embodiment includes a structural unit derived from a conjugated diene compound (hereinafter also referred to as a "conjugated diene monomer"). Specific examples of conjugated diene compounds are not particularly limited, and examples thereof include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-heptadiene. Among these, 1,3-butadiene and isoprene are preferred from the perspective of ease of industrial acquisition, and 1,3-butadiene is particularly preferred.
[0108] These may be used alone or in combination of two or more.
[0109] In addition, the hydrogenated conjugated diene polymer of the present embodiment preferably includes a structural unit from an aromatic vinyl compound (hereinafter also referred to as "aromatic vinyl monomer"). It should be noted that, in the hydrogenated conjugated diene polymer of the present embodiment, even when including a structural unit from an aromatic vinyl compound, the hydrogenated portion is preferably the portion from the conjugated diene compound, and the portion from the aromatic vinyl compound is not hydrogenated. As a specific example of an aromatic vinyl compound, it is not particularly limited, and examples thereof include styrene, p-methylstyrene, α-methylstyrene, vinyl ethylbenzene, vinyl xylene, vinyl naphthalene and diphenylethylene. Among these, styrene is preferred from the aspect of ease of industrial acquisition.
[0110] These may be used alone or in combination of two or more.
[0111] The hydrogenated conjugated diene polymer of the present embodiment is preferably a hydrogenated product of a copolymer of a conjugated diene compound and an aromatic vinyl compound (hereinafter also referred to as a "conjugated diene-aromatic vinyl copolymer").
[0112] As the so-called microstructure (ratio of the content of aromatic vinyl monomer and the amount of 1,2-vinyl bonds) of the copolymer of a conjugated diene compound and an aromatic vinyl compound, the content of the aromatic vinyl monomer is preferably 0 to 60% by mass, more preferably 3 to 60% by mass, further preferably 5 to 40% by mass, and the ratio of the amount of 1,2 vinyl bonds in the conjugated diene bond units in the conjugated diene polymer (1,2-vinyl bonds) is preferably 15 mol% to 70 mol%, more preferably 22 mol% to 65 mol%, further preferably 24 mol% to 60 mol%.
[0113] In the hydrogenated conjugated diene polymer of the present embodiment, the degree of branching is controlled by the amount of polymerization initiator added, the type (functional number) and amount of branching agent added, the type (functional number) and amount of coupling agent added, and the amount (type) of rubber softener added, and the influence of microstructure is small. Therefore, it can be appropriately designed within the range of the usual microstructure. However, as mentioned above, since the content of aromatic vinyl monomer and the amount of 1,2-vinyl bonds will affect the Tg of the hydrogenated conjugated diene polymer, it is preferably set within the above range from the perspective of fuel efficiency and braking performance.
[0114] Here, the content of the aromatic vinyl monomer can be determined by 1 H-NMR was used for measurement. Specifically, the measurement was performed according to the method described in the examples described later.
[0115] Here, when the conjugated diene polymer is a copolymer of butadiene and styrene, the vinyl bond amount (1,2-bond amount) in the butadiene bond unit can be determined by the Hampton method (RR Hampton, Analytical Chemistry, 21, 923 (1949)).
[0116] In the case where the hydrogenated conjugated diene polymer of the present embodiment is a hydrogenated product of a conjugated diene-aromatic vinyl copolymer, it is preferred that the number of blocks formed by linking more than 30 aromatic vinyl monomers is small or non-existent. More specifically, in the case where the copolymer is a butadiene-styrene copolymer, in a known method of decomposing the copolymer using the method of Kolthoff (IM KOLTHOFF, et al., J. Polym. Sci. 1, 429 (1946)) and analyzing the amount of polystyrene insoluble in methanol, the blocks formed by linking more than 30 aromatic vinyl monomers are preferably 10.0% by mass or less, more preferably 5.0% by mass or less relative to the total amount of the copolymer.
[0117] When the hydrogenated conjugated diene polymer of the present embodiment is a hydrogenated product of a conjugated diene-aromatic vinyl copolymer, it is preferred that the proportion of the aromatic vinyl monomer alone is high in order to improve fuel efficiency.
[0118] Specifically, when the copolymer is a butadiene-styrene copolymer, when the copolymer is decomposed by a method based on ozone decomposition known as the method of Tanaka et al. (Polymer, 22, 1721 (1981)) and the styrene linkage distribution is analyzed by GPC, it is preferred that the separated styrene amount is 40% by mass or more and the linked styrene structure with 8 or more styrene chains is 5.0% by mass or less relative to the total bonded styrene amount.
[0119] In this case, the hysteresis loss of the obtained vulcanized rubber is particularly low, which is preferable.
[0120] (Hydrogenation (hydrogenation) reaction)
[0121] The hydrogenated conjugated diene polymer of the present embodiment is obtained by hydrogenating (adding hydrogen to) a conjugated diene polymer described below. The method for hydrogenating the conjugated diene part of the conjugated diene polymer is not particularly limited, and a known method can be used.
[0122] As a suitable hydrogenation method, for example, there is a method of hydrogenation by blowing gaseous hydrogen into a polymer solution in the presence of a catalyst.
[0123] The catalyst is not particularly limited, and examples thereof include heterogeneous catalysts such as catalysts in which a noble metal is supported on a porous inorganic substance; catalysts in which salts of nickel, cobalt, etc. are made soluble and reacted with organic aluminum; and homogeneous catalysts such as catalysts using metallocenes such as cyclopentadienyl titanium. Among these, cyclopentadienyl titanium catalysts are preferred from the perspective of being able to select mild hydrogenation conditions.
[0124] The hydrogenation reaction may be a batch process or a continuous process, or a combination thereof.
[0125] Regarding the hydrogenation rate of the hydrogenated conjugated diene polymer of the present embodiment, the hydrogenation rate of the structural unit derived from the conjugated diene compound (e.g., butadiene) is 30% or more and less than 99%, preferably 30% or more and less than 96%, more preferably 30% or more and less than 93%, further preferably 30% or more and less than 90%, and particularly preferably 32% or more and less than 90%. In the hydrogenated conjugated diene polymer of the present embodiment, if the hydrogenation rate of the structural unit derived from the conjugated diene compound is 30% or more, it is excellent in terms of the breaking strength and elongation at break after being made into a sulfide, and if the hydrogenation rate of the structural unit derived from the conjugated diene compound is 99% or less, it is excellent in terms of the increase in crosslinking density after vulcanization, the breaking strength after being made into a sulfide, and the fuel efficiency performance.
[0126] On the other hand, from the perspective of fuel efficiency, the hydrogenation rate of the hydrogenated conjugated diene polymer of the present embodiment is preferably 80% or less, more preferably 75% or less, further preferably less than 75%, and particularly preferably less than 72%. In addition, from the perspective of strength such as breaking strength and elongation at break, the hydrogenation rate is preferably 39% or more, preferably 40% or more, more preferably 45% or more, further preferably 50% or more, and particularly preferably 55% or more. By setting the hydrogenation rate to a range of 39% to 80%, the loss modulus is reduced due to the butene chain generated by hydrogenation, and the increase in the loss modulus caused by the ethylene chain can be suppressed, so it is presumed that the fuel efficiency can be improved while maintaining the strength well.
[0127] The hydrogenated conjugated diene polymer compounded into the tire has various required functions due to the relationship with other components compounded into the tire, and the molecular weight, hydrogenation rate, and microstructure can be designed according to the required performance. For example, when strength such as breaking strength and elongation at break is required, the hydrogenation rate is preferably 65% or more, more preferably 70% or more, further preferably 75% or more, and particularly preferably 80% or more. On the other hand, when the hydrogenation rate is as high as more than 85%, it is sometimes difficult to exert the desired fuel-saving performance depending on the composition of other materials constituting the tire. Therefore, from the perspective of designing to achieve a balance between fuel-saving performance and strength, it is preferred to set the hydrogenation rate to 39% to 80%.
[0128] In addition, when the hydrogenation rate is as high as more than 75%, high viscosity may sometimes occur and processability may deteriorate. Therefore, when it is desired to increase the hydrogenation rate to more than 75%, from the perspective of viscosity and processability, the weight average molecular weight is preferably 1.2 million or less, more preferably 1 million or less, further preferably 800,000 or less, and particularly preferably 600,000 or less. In addition, when it is desired to increase the hydrogenation rate to more than 75%, from the perspective of suppressing high viscosity caused by the formation of crystalline components, it is preferred that the amount of aromatic vinyl is 15% by mass or more and / or the total content of the structure represented by the above formula (1) and formula (2) is 35 mol% or more.
[0129] For example, as a composition for improving strength such as breaking strength and breaking elongation, a resin component with a high glass transition temperature is sometimes mixed. From the aspect of strength, a high Tg resin component and a hydrogenated conjugated diene polymer with a high hydrogenation rate are a preferred combination. Preferred examples of the resin component are described below.
[0130] The hydrogenation rate can be controlled by the amount of hydrogen added relative to the structural unit derived from the conjugated diene compound, the hydrogen pressure, the reaction time, the amount of the hydrogenation catalyst added, and the solution viscosity.
[0131] The temperature of the hydrogenation reaction is not particularly limited, but is preferably 60°C to 105°C, more preferably 70°C to 100°C.
[0132] The hydrogenation rate can be determined by the following examples. 1 The measurement was performed by H-NMR.
[0133] The hydrogenated conjugated diene polymer of the present embodiment includes a structural unit derived from a conjugated diene compound, and preferably satisfies the following mathematical formula (S) when the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4) are respectively represented by a, b, c, and d in order in terms of their constituent ratios (mol%). It should be noted that the structural unit represented by formula (4) includes a 1,4 trans bond and a 1,4 cis bond.
[0134] [Chemistry 5]
[0135]
[0136] Mathematical formula (S): 20≤(a+b) / (a+b+c+d)×100≤65
[0137] The above formula (S) represents the weight ratio of 1,2-vinyl bonds and hydrogenated 1,2-vinyl bonds in the hydrogenated conjugated diene polymer. The hydrogenated conjugated diene polymer of the present embodiment has excellent balance among processability, fuel efficiency and wet grip performance when the above formula (S) is within this range.
[0138] The ratio of a, b, c, and d can be controlled by the type and amount of the polar substance added when polymerizing the conjugated diene polymer before hydrogenation, the polymerization temperature, and the amount of hydrogen in the reaction.
[0139] When the hydrogenation rate is controlled to be 40% to 80%, the content of 1,2 vinyl bonds is preferably small from the viewpoint of heat resistance. More specifically, the constituent ratio of a is preferably 10% or less, more preferably 8% or less, and further preferably 5% or less.
[0140] The hydrogenated conjugated diene polymer of the present embodiment contains a structural unit derived from a conjugated diene compound, and preferably satisfies the following mathematical formula (T) when the constituent ratios (mol %) of the structural unit represented by the above formula (1) and the structural unit represented by the above formula (2) are respectively represented by a and b.
[0141] Mathematical formula (T): 90≤(a) / (a+b)×100≤100
[0142] The above formula (T) represents the hydrogenation rate of the structure derived from the 1,2-vinyl bond, and the more the 1,2-vinyl bond is hydrogenated, the closer the value is to 100. In the hydrogenated conjugated diene polymer of the present embodiment, when the above formula (T) is 90 or more, the heat resistance tends to be excellent.
[0143] The ratio of a and b can be controlled by the type of hydrogenation catalyst, the hydrogenation reaction temperature, and the amount of hydrogen in the reaction.
[0144] It should be noted that in the present embodiment, the ratio of a, b, c and d can be measured by the method described in the examples described later.
[0145] (Degree of branching (Bn))
[0146] The hydrogenated conjugated diene polymer of the present embodiment has a degree of branching (Bn) as measured by a GPC-light scattering method with a viscosity detector (hereinafter also referred to as “degree of branching (Bn)”) of 2.5 or more, preferably 3.0 or more, more preferably 4.0 or more, further preferably 6.0 or more, further preferably 6.4 or more, still further preferably 8.0 or more, and particularly preferably 14.0 or more, from the viewpoint of suppressing the cold flow of the rubber compact and the processability.
[0147] The hydrogenated conjugated diene polymer of the present embodiment preferably has a higher degree of branching (Bn) as the molecular weight increases, and preferably has a higher degree of branching as the hydrogenation rate increases, from the viewpoint of achieving both processability and fuel efficiency.
[0148] In addition, when a cyclopentadienyl titanium catalyst is used as a hydrogenation catalyst, in the initial stage of the hydrogenation reaction, 1,2 vinyl bonds are hydrogenated, thereby reducing the solution viscosity and melt viscosity, but after the 1,2 vinyl bonds are hydrogenated, if the 1,4 bonds are hydrogenated, the solution viscosity and melt viscosity increase, so when it is desired to obtain a hydrogenated conjugated diene polymer with a hydrogenation rate exceeding 75%, it is preferred that the degree of branching (Bn) is high from the perspective of having a tendency to suppress viscosity even if the molecular weight is relatively high. If the degree of branching (Bn) is 6 or more, even when the hydrogenation rate exceeds 75%, there is a tendency to ensure the required processability when preparing the composition. On the other hand, in the region where the hydrogenation rate is 30% or more and 75% or less, the problem of viscosity increase is not likely to occur, so from the perspective of manufacturing, there is no need to perform high branching, and when it is desired to set the strength higher, the degree of branching (Bn) can be set to 2.5 or more, preferably 3.0 or more, preferably 30 or less, more preferably 20 or less, and further preferably 14 or less.
[0149] In the present embodiment, for example, the degree of branching (Bn) being 2 or more means that in the hydrogenated conjugated diene polymer of the present embodiment, there are two or more polymer chains in the side chains with respect to the substantially longest polymer main chain.
[0150] The degree of branching (Bn) of the hydrogenated conjugated diene polymer is defined as g'=6Bn / {(Bn+1)(Bn+2)} using the shrinkage factor (g') measured by GPC-light scattering method with a viscosity detector.
[0151] Generally, when compared with a linear polymer having the same absolute molecular weight, the molecular size of a polymer having branches tends to be smaller.
[0152] The shrinkage factor (g') is an index of the ratio of the size occupied by a molecule relative to a linear polymer assuming the same absolute molecular weight. That is, as the degree of branching of the polymer increases, the shrinkage factor (g') tends to decrease.
[0153] Regarding the shrinkage factor, in this embodiment, the intrinsic viscosity is used as an index of the molecular size, and the linear polymer is set to comply with the intrinsic viscosity [η] = -3.883M 0.771 In the above formula, M is the absolute molecular weight.
[0154] However, the shrinkage factor shows the rate of decrease in molecular size and does not accurately reflect the branching structure of the polymer.
[0155] Therefore, the branching degree (Bn) of the hydrogenated conjugated diene polymer is calculated using the contraction factor (g') value at each absolute molecular weight of the hydrogenated conjugated diene polymer. The calculated "branching degree (Bn)" accurately represents the number of polymers directly or indirectly bonded to each other on the longest main chain structure.
[0156] The calculated degree of branching (Bn) is an index representing the branch structure of the hydrogenated conjugated diene polymer.
[0157] For example, in the case of a common four-branched star polymer (four polymer chains connected in the center), two polymer chain arms are connected to the longest high-branch main chain structure, and the branching degree (Bn) is evaluated as 2.
[0158] In the case of a common 8-branched star polymer, 6 polymer chain arms are bonded to the longest high-branch main chain structure, and the branching degree (Bn) is evaluated as 6.
[0159] In the hydrogenated conjugated diene polymer of the present embodiment, the degree of branching (Bn) is 2.5 or more, which means that the hydrogenated conjugated diene polymer has the same branches as the star-shaped polymer structure having 4.5 branches on average.
[0160] Here, "branch" refers to a structure formed by direct or indirect bonding with other polymers relative to one polymer. In addition, "branching degree (Bn)" refers to the number of polymers directly or indirectly bonded to each other on the longest main chain structure.
[0161] By making the degree of branching (Bn) 2.5 or more, the hydrogenated conjugated diene polymer of the present embodiment can suppress the cold flow of the rubber compact, and the processability (handling property) when making a sulfide is extremely excellent, and the breaking strength and elongation at break after making a sulfide are excellent. From the same aspect, the degree of branching (Bn) of the hydrogenated conjugated diene polymer of the present embodiment is preferably 3.0 or more, more preferably 4.0 or more, further preferably 6.0 or more, further preferably 6.4 or more, further preferably 8.0 or more, and particularly preferably 14.0 or more.
[0162] The upper limit of the degree of branching (Bn) is not particularly limited and may be equal to or higher than the detection limit, but is preferably 84 or lower, more preferably 80 or lower, further preferably 64 or lower, and still more preferably 57 or lower.
[0163] The hydrogenated conjugated diene polymer of the present embodiment tends to have excellent breaking strength and breaking elongation when converted into a sulfide by setting the degree of branching (Bn) to 84 or less.
[0164] Generally, as the absolute molecular weight increases, the processability tends to deteriorate. When the absolute molecular weight increases in a linear polymer structure, the viscosity during the production of the sulfide increases significantly, and the processability deteriorates significantly.
[0165] Therefore, even if a large number of functional groups are introduced into the polymer to improve the affinity and / or reactivity with silicon oxide mixed as a filler, the silicon oxide cannot be fully dispersed in the polymer during the kneading process. As a result, the functions of the introduced functional groups cannot be exerted, and the effects of low hysteresis loss and improved anti-slip properties brought about by the introduction of the functional groups that should be expected cannot be exerted.
[0166] On the other hand, in the hydrogenated conjugated diene polymer of the present embodiment, by limiting the degree of branching (Bn) to 2.5 or more, the increase in viscosity during the production of sulfide accompanied by the increase in absolute molecular weight can be greatly suppressed, so it is speculated that, for example, it can be fully mixed with silicon oxide in the kneading process, and silicon oxide can be dispersed around the hydrogenated conjugated diene polymer. As a result, for example, the wear resistance and breaking strength can be improved by setting the molecular weight in the hydrogenated conjugated diene polymer to a large extent, and silicon oxide can be dispersed around the polymer by sufficient kneading, and the functional group can act and / or react, thereby presumably enabling it to have practically sufficient low hysteresis loss and wet skid resistance.
[0167] The absolute molecular weight of the hydrogenated conjugated diene polymer of this embodiment is preferably 25×10 4 Above 3000×10 4 Below, more preferably 26×104 Above 2500×10 4 Below, more preferably 28×10 4 Above 2000×10 4 the following.
[0168] From the perspective of moldability and processability of the rubber compact during production, the weight average molecular weight of the hydrogenated conjugated diene polymer of this embodiment is preferably 210,000 to less than 3,000,000, more preferably 220,000 to less than 2,500,000, and further preferably 230,000 to less than 2,300,000.
[0169] The method for controlling the weight average molecular weight to fall within the above range is not particularly limited, and examples thereof include a method of adjusting the amount of the polymerization initiator used.
[0170] The weight average molecular weight of the hydrogenated conjugated diene polymer according to the present embodiment can be measured by the method described in Examples.
[0171] From the aspects of processability, productivity and breaking strength, the hydrogenated conjugated diene polymer of this embodiment preferably has a component with a molecular weight of 300,000 or less (hereinafter also referred to as "component LM") of 20% to 80%, more preferably 20% to 75%, and more preferably 21% to 70%.
[0172] The method for controlling the ratio of the component LM within the above range is not particularly limited, and examples thereof include a method of adjusting the amount of a polymerization initiator used and a method of adjusting the amount of a coupling agent used.
[0173] The ratio of the component LM in the hydrogenated conjugated diene polymer of the present embodiment can be measured by the method described in Examples.
[0174] From the perspective of suppressing the reduction in yield due to powder formation in the drying process during production, the Mooney viscosity of the hydrogenated conjugated diene polymer of the present embodiment using an L-shaped rotor at 100° C. is preferably 120 or less, more preferably 110 or less, further preferably 100 or less, and particularly preferably 90 or less. In addition, from the perspective of tensile strength, the Mooney viscosity is preferably 30 or more, more preferably 40 or more, and further preferably 50 or more.
[0175] The method for controlling the Mooney viscosity at 100° C. using an L-shaped rotor to fall within the above range is not particularly limited, and examples thereof include adjusting the amount of polymerization initiator, the type and amount of branching agent, and the type and amount of coupling agent.
[0176] Even if the Mooney viscosity is the same, a higher degree of branching is preferred because it can increase the molecular weight.
[0177] The Mooney viscosity of the hydrogenated conjugated diene polymer according to the present embodiment at 100° C. using an L-shaped rotor can be measured by the method described in Examples.
[0178] The degree of branching (Bn) of the hydrogenated conjugated diene polymer can be controlled to be above 2.5 by the combination of the amount of branching agent added and the amount of terminal coupling agent added described later. Specifically, the control of the degree of branching can be controlled by the number of functional groups of the branching agent, the amount of branching agent added, the timing of adding the branching agent, the number of functions of the coupling agent or the modifier containing nitrogen atoms, and the amount of the coupling agent or the modifier containing nitrogen atoms. More specifically, as described in the method for producing the hydrogenated conjugated diene polymer described below.
[0179] (coupling)
[0180] The hydrogenated conjugated diene polymer of the present embodiment is preferably a conjugated diene polymer obtained by coupling the active ends of the conjugated diene polymer obtained through polymerization and branching steps using a branching agent and a trifunctional or higher-functional reactive compound (hereinafter also referred to as a "coupling agent").
[0181] In the coupling step, a coupling agent or a coupling agent having a nitrogen atom-containing group is used to couple one end of the active terminal of the conjugated diene polymer to obtain the conjugated diene polymer. More specifically, as described in the method for producing the conjugated diene polymer described below.
[0182] (Coupling agent)
[0183] In this embodiment, the coupling agent used in the coupling step may have any structure as long as it is a trifunctional or higher-functional reactive compound, and is preferably a trifunctional or higher-functional reactive compound having a silicon atom. More specifically, it is as described in the method for producing a hydrogenated conjugated diene polymer described below.
[0184] The hydrogenated conjugated diene polymer of the present embodiment preferably contains a nitrogen atom. The hydrogenated conjugated diene polymer containing a nitrogen atom can be obtained, for example, by a coupling reaction using a modifying agent having a nitrogen atom-containing group described below.
[0185] (Modifier having a nitrogen atom-containing group)
[0186] The hydrogenated conjugated diene polymer of the present embodiment is more preferably a conjugated diene polymer obtained by coupling the conjugated diene polymer obtained through the polymerization and branching steps with a reactive compound having a nitrogen atom-containing group or more (hereinafter also referred to as a "modifier having a nitrogen atom-containing group") at the active end of the conjugated diene polymer.
[0187] In the coupling step, a coupling reaction is performed on one of the active ends of the conjugated diene polymer using a coupling agent having a nitrogen atom-containing group to obtain a conjugated diene polymer.
[0188] Conjugated diene polymers obtained by coupling using a modifier having a nitrogen atom-containing group have good dispersibility of silicon oxide when mixed with a filler or the like to form a composition, good processability of the composition obtained by mixing with the filler or the like, and good wear resistance and breaking strength after the composition is made into a sulfide, and tend to significantly improve the balance between low hysteresis loss and wet skid resistance. More specifically, as described in the method for producing a hydrogenated conjugated diene polymer described below.
[0189] Examples of the modifier having a nitrogen atom-containing group include, but are not limited to, isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, nitrogen-containing carbonyl compounds, nitrogen-containing vinyl compounds, nitrogen-containing epoxy compounds, and the like.
[0190] The modifier having a nitrogen atom-containing group preferably has a nitrogen atom-containing functional group, and the nitrogen atom-containing functional group is preferably an amine compound having no active hydrogen, and examples thereof include tertiary amine compounds, protected amine compounds in which the above active hydrogen is substituted with a protecting group, imine compounds represented by the general formula -N=C, and alkoxysilane compounds bonded to the above nitrogen atom-containing group. More specifically, as described in the method for producing a hydrogenated conjugated diene polymer described below.
[0191] (Modification rate)
[0192] In the present specification, the “modification ratio” refers to the mass ratio of the conjugated diene polymer or hydrogenated conjugated diene polymer having a nitrogen atom-containing functional group relative to the total amount of the conjugated diene polymer or hydrogenated conjugated diene polymer.
[0193] For example, when a nitrogen-containing modifier is reacted with a terminal end, the mass ratio of the conjugated diene polymer having a nitrogen-containing functional group based on the nitrogen-containing modifier to the total amount of the conjugated diene polymer is expressed as the modification rate.
[0194] On the other hand, when a polymer is branched using a branching agent containing a nitrogen atom, the resulting conjugated diene polymer also has a nitrogen atom-containing functional group, and therefore the branched polymer is also included in the calculation of the modification ratio.
[0195] That is, in this specification, the total mass ratio of the coupled polymer based on the modifying agent having a nitrogen atom-containing functional group and / or the branched polymer based on the branching agent having a nitrogen atom-containing functional group is referred to as the "modification ratio".
[0196] In the hydrogenated conjugated diene polymer of the present embodiment, at least one end is modified with a nitrogen atom-containing group, thereby having a tendency to dramatically improve the balance between low hysteresis loss and wet skid resistance while maintaining the processability when the composition is prepared by mixing fillers, etc., and the wear resistance and breaking strength after the composition is prepared as a sulfide.
[0197] In the hydrogenated conjugated diene polymer of the present embodiment, from the aspects of processability, wear resistance, breaking strength, and the balance between low hysteresis loss and anti-wet skid resistance, the modification rate measured by column adsorption GPC method (hereinafter also referred to as "modification rate") is preferably 40% by mass or more relative to the total amount of the hydrogenated conjugated diene polymer.
[0198] The modification rate is preferably 60% by mass or more, more preferably 65% by mass or more, further preferably 70% by mass or more, and still more preferably 80% by mass or more. The upper limit of the modification rate is not particularly limited, and is, for example, 99% by mass.
[0199] The modification rate can be measured by a chromatography method capable of separating modified components containing a functional group from non-modified components.
[0200] Examples of a method using this chromatography include a method using a gel permeation chromatography column filled with a polar substance such as silicon oxide that adsorbs specific functional groups and performing quantitative determination by comparison with an internal standard of a non-adsorbed component (column adsorption GPC method).
[0201] More specifically, the adsorption amount on the silica column is measured from the difference between the chromatogram obtained by measuring a sample solution containing the sample and low molecular weight internal standard polystyrene using a polystyrene gel column and the chromatogram obtained by measuring using a silica column, thereby obtaining the modification rate.
[0202] More specifically, the modification ratio can be measured by the method described in Examples.
[0203] In the hydrogenated conjugated diene polymer of the present embodiment, the modification ratio can be controlled to 40% by mass or more by adjusting the amount of the modifier added and the reaction method.
[0204] For example, the following methods can be combined to control the polymerization conditions, thereby achieving the above-mentioned modification rate: a method of using an organic lithium compound having at least one nitrogen atom in the molecule described later as a polymerization initiator to carry out polymerization; a method of copolymerizing a monomer having at least one nitrogen atom in the molecule; a method of using a modifier of the structural formula described later.
[0205] The "star-shaped polymer structure" as used herein refers to a structure in which a plurality of polymer chains (arms) are linked via one central branch point.
[0206] In addition, the one central branch point mentioned here has a substituent containing an atom derived from a coupling agent or a nitrogen atom derived from a modifier.
[0207] The "main chain branch structure" as used herein means a structure in which a polymer chain forms a branch point at a portion derived from a vinyl monomer containing an alkoxysilyl group or a halosilyl group, and a polymer chain (arm) extends from the branch point.
[0208] In the hydrogenated conjugated diene polymer of the present embodiment, from the aspect of increasing the degree of branching (Bn), the main chain branching points composed of the part derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group are preferably 3 or more, and the branch structure derived from the star-shaped polymer structure formed by the coupling agent in the reaction step is preferably 3 or more, more preferably 4 or more, and further preferably 8 or more.
[0209] It should be noted that, when modification is performed using a star-shaped coupling agent and when a branching agent is introduced into the polymer, the degree of branching (Bn) increases, but when the coupling agent is used to branch the entire polymer chain, the contribution to the degree of branching (Bn) is greater.
[0210] In the design of the polymer, the degree of branching (Bn) can be controlled by selecting a coupling agent and selecting the type and amount of the branching agent, but by also taking the contribution rate into consideration, the control of the degree of branching (Bn) becomes easier.
[0211] (Main chain branch structure)
[0212] The main chain branch structure has two or more branching points, preferably three or more branching points, and more preferably four or more branching points, as measured by the branching points of the portion derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group.
[0213] In addition, the branching point forming the main chain branch structure preferably has at least two polymer chains, and more preferably has three or more non-main chain polymer chains.
[0214] In particular, in the main chain branch structure formed by a vinyl monomer containing an alkoxysilyl group or a halosilyl group, 29 When the signal was detected by Si-NMR, a peak derived from the main chain branch structure was detected in the range of -45 ppm to -65 ppm, and more specifically in the range of -50 ppm to -60 ppm.
[0215] (Star-shaped polymer structure)
[0216] The hydrogenated conjugated diene polymer of the present embodiment preferably has a star-shaped polymer structure, and the number of branches derived from the star-shaped polymer structure is preferably 3 or more, more preferably 4 or more, further preferably 6 or more, and still more preferably 8 or more. The upper limit of the number of branches derived from the star-shaped polymer structure is not particularly limited, and is, for example, 32 or less.
[0217] The hydrogenated conjugated diene polymer of the present embodiment preferably has a star-shaped polymer structure with three or more branches, and has a portion derived from a vinyl monomer containing an alkoxysilyl group or a halosilyl group on at least one branch of the star-shaped structure, and has a further main chain branch structure on the portion derived from a vinyl monomer containing an alkoxysilyl group or a halosilyl group. Regarding the method for obtaining such a hydrogenated conjugated diene polymer, the above-mentioned "star-shaped polymer structure" can be formed by adjusting the number of functional groups of the coupling agent and the amount of the coupling agent added, and the "main chain branch structure" can be controlled by adjusting the number of functional groups of the branching agent, the amount of the branching agent added, and the timing of adding the branching agent.
[0218] In order to obtain a hydrogenated conjugated diene polymer (which is a hydrogenated conjugated diene polymer having a star-shaped polymer structure with more than three branches, wherein at least one branch of the star-shaped structure has a portion derived from a vinyl monomer containing an alkoxysilyl group or a halosilyl group, and the portion derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group has a further main chain branch structure), the following method can be cited, for example: polymerization is carried out using an organic lithium compound as a polymerization initiator, a branching agent that provides specific branching points is further added during or after the polymerization, the polymerization is continued, and then modification is carried out using a modifier that imparts a specific branching rate.
[0219] Such means for controlling polymerization conditions are described in the production method in the examples described later.
[0220] (Detailed structure of the main chain branch structure)
[0221] In the hydrogenated conjugated diene polymer of the present embodiment, it is preferred that the portion derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group is a monomer unit based on a compound represented by the following formula (5) or (6), and that the polymer chain has branching points brought about by the monomer unit based on the compound represented by the following formula (5) or (6). In addition, it is more preferred that the hydrogenated conjugated diene polymer is obtained using a coupling agent, and it is further preferred that at least one end of the hydrogenated conjugated diene polymer is coupled using a coupling agent. It is further preferred that at least one end of the hydrogenated conjugated diene polymer is modified using a nitrogen atom-containing group.
[0222] [Chemistry 6]
[0223]
[0224] [Chemistry 7]
[0225]
[0226] (In formula (5), R 1 The group represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and a part of the group may have a branched structure.
[0227] R 2 ~R 3 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure. 1 ~R 3 Each one is independent.
[0228] X 1 represents a halogen atom. When there are plural X 1 Each one is independent.
[0229] m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3. (m+n+l) represents 3.)
[0230] (In formula (6), R 2 ~R 5 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure.
[0231] When there are multiple R 2 ~R 5 Each one is independent.
[0232] X 2 ~X 3 Each independently represents a halogen atom. When there are plural X 2 ~X 3 Each one is independent.
[0233] m represents an integer of 0 to 2, n represents an integer of 0 to 3, and l represents an integer of 0 to 3.
[0234] (m+n+l) means 3.
[0235] a represents an integer from 0 to 2, b represents an integer from 0 to 3, and c represents an integer from 0 to 3. (a+b+c) represents 3.)
[0236] The hydrogenated conjugated diene polymer of the present embodiment is preferably a hydrogenated conjugated diene polymer having a monomer unit based on a compound represented by the above formula (5), wherein R1 is a hydrogen atom, and m = 0. This increases the number of branches, thereby achieving an effect of improving wear resistance and processability.
[0237] The hydrogenated conjugated diene polymer of the present embodiment is preferably a conjugated diene polymer having a monomer unit based on a compound represented by the above formula (6), wherein m = 0 and b = 0. This can improve wear resistance and processability.
[0238] In addition, the hydrogenated conjugated diene polymer of the present embodiment is preferably a hydrogenated conjugated diene polymer having a monomer unit based on a compound represented by the above formula (6), wherein m = 0, l = 0, n = 3, a = 0, b = 0, and c = 3. This can achieve the effect of improving wear resistance and processability.
[0239] The hydrogenated conjugated diene polymer of the present embodiment is more preferably a hydrogenated conjugated diene polymer having a monomer unit based on a compound represented by the above formula (5), wherein R 1 is a hydrogen atom, m = 0, l = 0, and n = 3. This can increase the modification rate and the degree of branching, thereby achieving the effect of improving fuel efficiency, wear resistance, and processability.
[0240] (Branching Agent)
[0241] In the hydrogenated conjugated diene polymer of the present embodiment, when constructing a main chain branch structure, it is preferable to use a branching agent represented by the following formula (5) or formula (6) as a branching agent.
[0242] [Chemistry 8]
[0243]
[0244] [Chemistry 9]
[0245]
[0246] (In formula (5), R 1 The group represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and a part of the group may have a branched structure.
[0247] R 2 ~R 3 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure.
[0248] When there are multiple R 1 ~R 3 Each one is independent.
[0249] X1 represents a halogen atom. When there are plural X 1 Each one is independent.
[0250] m represents an integer of 0 to 2, n represents an integer of 0 to 3, and l represents an integer of 0 to 3.
[0251] (m+n+1) means 3.)
[0252] (In formula (6), R 2 ~R 5 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure.
[0253] When there are multiple R 2 ~R 5 Each one is independent.
[0254] X 2 ~X 3 Each independently represents an independent halogen atom. When there are plural X 2 ~X 3 Each one is independent.
[0255] m represents an integer of 0 to 2, n represents an integer of 0 to 3, and l represents an integer of 0 to 3.
[0256] (m+n+l) means 3.
[0257] a represents an integer from 0 to 2, b represents an integer from 0 to 3, and c represents an integer from 0 to 3. (a+b+c) represents 3.)
[0258] In this embodiment, from the perspective of polymerization sustainability and increasing the degree of branching, the branching agent used to construct the main chain branch structure of the hydrogenated conjugated diene polymer is preferably R of formula (5): 1 A compound in which m is a hydrogen atom and m=0.
[0259] In the present embodiment, from the viewpoint of increasing the degree of branching, the branching agent used when constructing the main chain branch structure of the hydrogenated conjugated diene polymer is preferably a compound wherein m=0 and b=0 in formula (6).
[0260] In this embodiment, from the perspective of polymerization sustainability and improving the modification rate and branching degree, the branching agent used when constructing the main chain branch structure of the hydrogenated conjugated diene polymer is more preferably R of formula (5): 1 A compound wherein m=0, l=0, and n=3 is a hydrogen atom.
[0261] In addition, in the present embodiment, from the perspective of improving the modification rate and the degree of branching, the branching agent used when constructing the main chain branch structure of the hydrogenated conjugated diene polymer is preferably a compound wherein m=0, l=0, n=3, a=0, b=0, and c=3 in the above formula (6).
[0262] Examples of the branching agent represented by the above formula (5) include, but are not limited to:
[0263] Trimethoxy(4-vinylphenyl)silane, triethoxy(4-vinylphenyl)silane, tripropoxy(4-vinylphenyl)silane, tributoxy(4-vinylphenyl)silane, triisopropoxy(4-vinylphenyl)silane, trimethoxy(3-vinylphenyl)silane, triethoxy(3-vinylphenyl)silane, tripropoxy(3-vinylphenyl)silane, tributoxy(3-vinylphenyl)silane, triisopropoxy(3-vinylphenyl)silane, trimethoxy(2-vinylphenyl)silane, triethoxy(2-vinylphenyl)silane, tripropoxy(2-vinylphenyl)silane, tributoxy(2-vinylphenyl)silane, triisopropoxy(2-vinylphenyl)silane, trimethoxy(4-vinylphenyl)silane, triethoxy(4-vinylphenyl)silane, triisopropoxy(4-vinylphenyl)silane, triisopropoxy(4-vinylphenyl)silane, trimethoxy(3-vinylphenyl)silane, triethoxy(3-vinylphenyl)silane, tripropoxy(3-vinylphenyl)silane, tributoxy(3-vinylphenyl)silane, triisopropoxy(3-vinylphenyl)silane, triisopropoxy(2 ... methyl(4-vinylphenyl)silane, diethoxymethyl(4-vinylphenyl)silane, dipropoxymethyl(4-vinylphenyl)silane, dibutoxymethyl(4-vinylphenyl)silane, diisopropoxymethyl(4-vinylphenyl)silane, dimethoxymethyl(3-vinylphenyl)silane, diethoxymethyl(3-vinylphenyl)silane, dipropoxymethyl(3-vinylphenyl)silane, dibutoxymethyl(3-vinylphenyl)silane, diisopropoxymethyl(3-vinylphenyl)silane, dimethoxymethyl(2-vinylphenyl)silane, diethoxymethyl(2-vinylphenyl)silane, dipropoxymethyl(2-vinylphenyl)silane, dibutoxymethyl(2-vinylphenyl)silane, Diisopropoxymethyl (2-vinylphenyl) silane, dimethylmethoxy (4-vinylphenyl) silane, dimethylethoxy (4-vinylphenyl) silane, dimethylpropoxy (4-vinylphenyl) silane, dimethylbutoxy (4-vinylphenyl) silane, dimethylisopropoxy (4-vinylphenyl) silane, dimethylmethoxy (3-vinylphenyl) silane, dimethylethoxy (3-vinylphenyl) silane, dimethylpropoxy (3-vinylphenyl) silane, dimethylbutoxy (3-vinylphenyl) silane, dimethylisopropoxy (3-vinylphenyl) silane, dimethylmethoxy (2-vinylphenyl) silane, dimethylethoxy (2-vinylphenyl) silane, dimethylpropoxy (2-vinylphenyl) silane phenyl) silane, dimethylbutyloxy (2-vinylphenyl) silane, dimethylisopropoxy (2-vinylphenyl) silane, trimethoxy (4-isopropenylphenyl) silane, triethoxy (4-isopropenylphenyl) silane, tripropoxy (4-isopropenylphenyl) silane, tributoxy (4-isopropenylphenyl) silane, triisopropoxy (4-isopropenylphenyl) silane, trimethoxy (3-isopropenylphenyl) silane, triethoxy (3-isopropenylphenyl) silane, tripropoxy (3-isopropenylphenyl) silane, tributoxy (3-isopropenylphenyl) silane, triisopropoxy (3-isopropenylphenyl) silane, trimethoxy (2-isopropenylphenyl) silane, triethoxy (2-isopropenylphenyl) silane,Tripropoxy(2-isopropenylphenyl)silane, tributoxy(2-isopropenylphenyl)silane, triisopropoxy(2-isopropenylphenyl)silane, dimethoxymethyl(4-isopropenylphenyl)silane, diethoxymethyl(4-isopropenylphenyl)silane, dipropoxymethyl(4-isopropenylphenyl)silane, dibutoxymethyl(4-isopropenylphenyl)silane, diisopropoxymethyl(4-isopropenylphenyl)silane, dimethoxymethyl(3-isopropenylphenyl)silane, diethoxymethyl(3-isopropenylphenyl)silane, dipropoxymethyl(3-isopropenylphenyl)silane, dibutoxymethyl(3-isopropenylphenyl)silane, diisopropoxymethyl(4-isopropenylphenyl)silane, Propoxymethyl (3-isopropenylphenyl) silane, dimethoxymethyl (2-isopropenylphenyl) silane, diethoxymethyl (2-isopropenylphenyl) silane, dipropoxymethyl (2-isopropenylphenyl) silane, dibutoxymethyl (2-isopropenylphenyl) silane, diisopropoxymethyl (2-isopropenylphenyl) silane, dimethylmethoxy (4-isopropenylphenyl) silane, dimethylethoxy (4-isopropenylphenyl) silane, dimethylpropoxy (4-isopropenylphenyl) silane, dimethylbutoxy (4-isopropenylphenyl) silane, dimethylisopropoxy (4-isopropenylphenyl) silane, dimethylmethoxy (3-isopropenylphenyl) Silane, dimethylethoxy (3-isopropenylphenyl) silane, dimethylpropoxy (3-isopropenylphenyl) silane, dimethylbutoxy (3-isopropenylphenyl) silane, dimethylisopropoxy (3-isopropenylphenyl) silane, dimethylmethoxy (2-isopropenylphenyl) silane, dimethylethoxy (2-isopropenylphenyl) silane, dimethylpropoxy (2-isopropenylphenyl) silane, dimethylbutoxy (2-isopropenylphenyl) silane, dimethylisopropoxy (2-isopropenylphenyl) silane, trichloro (4-vinylphenyl) silane, trichloro (3-vinylphenyl) silane, trichloro (2-vinylphenyl) silane, tribromo (4-vinylphenyl) silane phenyl) silane, tribromo(3-vinylphenyl) silane, tribromo(2-vinylphenyl) silane, dichloromethyl(4-vinylphenyl) silane, dichloromethyl(3-vinylphenyl) silane, dichloromethyl(2-vinylphenyl) silane, dibromomethyl(4-vinylphenyl) silane, dibromomethyl(3-vinylphenyl) silane, dibromomethyl(2-vinylphenyl) silane, dimethylchloro(4-vinylphenyl) silane, dimethylchloro(3-vinylphenyl) silane, dimethylchloro(2-vinylphenyl) silane, dimethylbromo(4-vinylphenyl) silane, dimethylbromo(3-vinylphenyl) silane, dimethylbromo(2-vinylphenyl) silane.
[0264] Among these, trimethoxy(4-vinylphenyl)silane, triethoxy(4-vinylphenyl)silane, tripropoxy(4-vinylphenyl)silane, tributoxy(4-vinylphenyl)silane, triisopropoxy(4-vinylphenyl)silane, trimethoxy(3-vinylphenyl)silane, triethoxy(3-vinylphenyl)silane, tripropoxy(3-vinylphenyl)silane, tributoxy(3-vinylphenyl)silane, triisopropoxy(3-vinylphenyl)silane, and trichloro(4-vinylphenyl)silane are preferred, and trimethoxy(4-vinylphenyl)silane, triethoxy(4-vinylphenyl)silane, tripropoxy(4-vinylphenyl)silane, tributoxy(4-vinylphenyl)silane, and triisopropoxy(4-vinylphenyl)silane are more preferred.
[0265] Examples of the branching agent represented by the above formula (6) include, but are not limited to:
[0266] 1,1-bis(4-trimethoxysilylphenyl)ethylene, 1,1-bis(4-triethoxysilylphenyl)ethylene, 1,1-bis(4-tripropoxysilylphenyl)ethylene, 1,1-bis(4-tripentoxysilylphenyl)ethylene, 1,1-bis(4-triisopropoxysilylphenyl)ethylene, 1,1-bis(3-trimethoxysilylphenyl)ethylene, 1,1-bis(3-triethoxysilylphenyl)ethylene, 1,1-bis(3-tripentoxysilylphenyl)ethylene, 1,1-bis(3-tripentoxysilylphenyl)ethylene, 1,1-bis(3-triisopropoxysilylphenyl)ethylene, 1,1-bis(2-trimethoxysilylphenyl)ethylene, 1,1-bis(2-triethoxysilylphenyl)ethylene, 1,1-bis(3-tripropoxysilylphenyl)ethylene, 1,1-bis(2-tripentyloxysilylphenyl)ethylene, 1,1-bis(2-triisopropoxysilylphenyl)ethylene, 1,1-bis(4-(dimethylmethoxysilyl)phenyl)ethylene, 1,1-bis(4-(diethylmethoxysilyl)phenyl)ethylene, 1,1-bis(4-(dipropylmethoxysilyl)phenyl)ethylene, 1,1-bis(4-(dimethylethoxysilyl)phenyl)ethylene, 1,1-bis(4-(diethylethoxysilyl)phenyl)ethylene, 1,1-bis(4-(dipropylethoxysilyl)phenyl)ethylene.
[0267] Among these, 1,1-bis(4-trimethoxysilylphenyl)ethylene, 1,1-bis(4-triethoxysilylphenyl)ethylene, 1,1-bis(4-tripropoxysilylphenyl)ethylene, 1,1-bis(4-tripentoxysilylphenyl)ethylene, and 1,1-bis(4-triisopropoxysilylphenyl)ethylene are preferred, and 1,1-bis(4-trimethoxysilylphenyl)ethylene is more preferred.
[0268] (Method for producing hydrogenated conjugated diene polymer)
[0269] The method for producing the hydrogenated conjugated diene polymer of the present embodiment, for example, includes the following steps (A) and (E), and further includes at least one of the following steps (B) and (D). In the hydrogenated conjugated diene polymer obtained in step (E), the degree of branching (Bn) obtained by the GPC-light scattering method with a viscosity detector is more than 2.5, and the hydrogenation rate of the structural unit from the conjugated diene compound is more than 30% and less than 99%. In addition, the method for producing the hydrogenated conjugated diene polymer of the present embodiment preferably includes step (D). In addition, the method for producing the hydrogenated conjugated diene polymer of the present embodiment preferably further includes the following step (C).
[0270] Step (A): A step of polymerizing a conjugated diene compound alone or a conjugated diene compound and an aromatic vinyl compound to obtain a conjugated diene polymer (polymerization step).
[0271] Step (B): a step of reacting a branching agent with a conjugated diene polymer terminal to obtain a conjugated diene polymer solution containing a branched conjugated diene polymer having an active terminal (branching step).
[0272] Step (C): A step of further polymerizing a conjugated diene compound alone or a conjugated diene compound and an aromatic vinyl compound from the terminal of the conjugated diene polymer to obtain a conjugated diene polymer (polymerization step).
[0273] Step (D): a step of reacting a coupling agent with the terminal of a conjugated diene polymer (coupling step).
[0274] Step (E): A step of subjecting the conjugated diene polymer to a hydrogenation reaction to obtain a hydrogenated conjugated diene polymer (hydrogenation step).
[0275] Each process preferably includes at least one process from process (B) to (D) after process (A), and then preferably implements process (E). For example, in the case where the branching agent of process (B) is added in the middle of the polymerization process of process (A), that is, before the monomer is completely consumed, the branch chain should be extended even if no further monomer is added after the branching agent reacts, so this is equivalent to process (C). However, from the perspective of managing the process and producing a polymer with a target structure, it is a preferred method to add a branching agent after the monomer consumption of process (A) is completed, and then after the branching agent is combined with the polymer chain, further add a monomer as process (C) to extend the branch chain. In addition, from the perspective of increasing the reaction rate of the coupling agent in process (D), it is preferred to add a conjugated diene as an additional monomer or to increase the supply ratio of the conjugated diene for addition.
[0276] Steps (B) to (D) may be performed only once, or may be repeated two or more times.
[0277] As the method for producing a hydrogenated conjugated diene polymer according to the present embodiment, it is particularly preferred to carry out the method in the order of step (A), step (B), step (C), step (D), and step (E); or in the order of step (A), step (D), and step (E); or in the order of step (A), step (C), step (D), and step (E); or in the order of step (A), step (B), and step (E).
[0278] In the above step (A) of the method for producing a hydrogenated conjugated diene polymer of the present embodiment, in the presence of an organic lithium compound, an organic lithium compound is used as a polymerization initiator to polymerize at least a conjugated diene compound. The hydrogenated conjugated diene polymer may be a hydrogenated product of any one of a homopolymer of a single conjugated diene compound, a polymer of different types of conjugated diene compounds, i.e., a copolymer, and a copolymer of a conjugated diene compound and an aromatic vinyl compound.
[0279] (Polymerization initiator)
[0280] As the polymerization initiator, at least an organic monolithium compound can be used.
[0281] Examples of the organic monolithium compound include, but are not limited to, low molecular weight compounds and soluble oligomer organic monolithium compounds.
[0282] In addition, examples of the organic monolithium compound include compounds having a carbon-lithium bond, compounds having a nitrogen-lithium bond, and compounds having a tin-lithium bond in terms of the bonding form between the organic group and the lithium.
[0283] The amount of the organic monolithium compound used as a polymerization initiator is preferably determined according to the molecular weight of the desired conjugated diene polymer or hydrogenated conjugated diene polymer.
[0284] The amount of the monomer such as the conjugated diene compound used relative to the amount of the polymerization initiator used is correlated with the degree of polymerization, that is, it tends to be correlated with the number average molecular weight and / or the weight average molecular weight.
[0285] Therefore, in order to increase the molecular weight, the amount of the polymerization initiator used can be adjusted in the direction of decreasing, and in order to decrease the molecular weight, the amount of the polymerization initiator used can be adjusted in the direction of increasing.
[0286] From the viewpoint of being used in a method of introducing nitrogen atoms into a conjugated diene polymer, the organic monolithium compound is preferably an alkyllithium compound having a substituted amino group or a dialkyllithium amide.
[0287] In this case, a conjugated diene polymer having a nitrogen atom derived from an amino group at the polymerization initiation terminal is obtained.
[0288] The substituted amino group is an amino group having no active hydrogen or a structure in which the active hydrogen is protected.
[0289] Examples of the alkyl lithium compound having an amino group without active hydrogen include, but are not limited to, 3-dimethylaminopropyl lithium, 3-diethylaminopropyl lithium, 4-(methylpropylamino)butyl lithium and 4-hexamethyleneiminobutyl lithium.
[0290] Examples of the alkyl lithium compound having an amino group with active hydrogen protected include, but are not limited to, 3-bistrimethylsilylaminopropyllithium and 4-trimethylsilylmethylaminobutyllithium.
[0291] Examples of the dialkyl lithium amide include, but are not limited to, dimethyl lithium amide, diethyl lithium amide, dipropyl lithium amide, dibutyl lithium amide, di-n-hexyl lithium amide, diheptyl lithium amide, diisopropyl lithium amide, dioctyl lithium amide, di-2-ethylhexyl lithium amide, didecyl lithium amide, ethylpropyl lithium amide, ethylbutyl lithium amide, ethylbenzyl lithium amide, methylphenethyl lithium amide, hexamethylene imide, lithium pyrrolidine, lithium piperidine, lithium heptamethylene imide, lithium morpholine, 1-lithium azacyclooctane, 6-lithium-1,3,3-trimethyl-6-azabicyclo[3.2.1]octane and 1-lithium-1,2,3,6-tetrahydropyridine.
[0292] These organic monolithium compounds having a substituted amino group can also be used as organic monolithium compounds of solubilized oligomers by reacting a small amount of a polymerizable monomer such as 1,3-butadiene, isoprene, or styrene.
[0293] As the organic monolithium compound, an alkyl lithium compound is preferred from the viewpoint of ease of industrial availability and ease of control of the polymerization reaction. In this case, a conjugated diene polymer having an alkyl group at the polymerization initiation terminal can be obtained.
[0294] Examples of the alkyl lithium compound include, but are not limited to, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, n-hexyl lithium, benzyl lithium, phenyl lithium, and stilbene lithium.
[0295] As the alkyl lithium compound, n-butyl lithium and sec-butyl lithium are preferred from the viewpoint of ease of industrial availability and ease of control of the polymerization reaction.
[0296] These organic monolithium compounds may be used alone or in combination of two or more, or may be used in combination with other organic metal compounds.
[0297] Examples of the other organic metal compounds include alkaline earth metal compounds, other alkali metal compounds, and other organic metal compounds.
[0298] Examples of the alkaline earth metal compound include, but are not limited to, organomagnesium compounds, organocalcium compounds, and organostrontium compounds, and examples also include alkoxides, sulfonates, carbonates, and amide compounds of alkaline earth metals.
[0299] Examples of the organomagnesium compound include dibutylmagnesium and ethylbutylmagnesium. Examples of other organometallic compounds include organoaluminum compounds.
[0300] In the polymerization step, examples of the polymerization reaction mode include, but are not limited to, a batch-type (also referred to as a "batch-type") and a continuous-type polymerization reaction mode.
[0301] In the continuous method, one or more connected reactors can be used. The continuous reactor, for example, uses a tank-type or tube-type reactor with a stirrer. In the continuous method, preferably, monomers, an inert solvent, and a polymerization initiator are continuously loaded into the reactor, a polymer solution containing a polymer is obtained in the reactor, and the polymer solution is continuously discharged.
[0302] The batch reactor is, for example, a tank reactor with a stirrer. In the batch reactor, preferably, monomers, an inert solvent and a polymerization initiator are loaded, and monomers are added continuously or intermittently during the polymerization as required to obtain a polymer solution containing a polymer in the reactor, and the polymer solution is discharged after the polymerization is completed.
[0303] In the method for producing a hydrogenated conjugated diene polymer of the present embodiment, a continuous method is preferred in which the polymer can be continuously discharged and supplied to the next reaction in a short time in order to obtain a conjugated diene polymer having active terminals at a high ratio.
[0304] The polymerization process of the conjugated diene polymer is preferably carried out in an inert solvent. The solvent is not particularly limited, and examples thereof include hydrocarbon solvents such as saturated hydrocarbons and aromatic hydrocarbons. Specific hydrocarbon solvents include, but are not limited to, aliphatic hydrocarbons such as butane, pentane, hexane, and heptane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, and methylcyclohexane; aromatic hydrocarbons such as benzene, toluene, and xylene, and hydrocarbons consisting of mixtures thereof.
[0305] By treating allenes and acetylenes as impurities with an organic metal compound before subjecting them to the polymerization reaction, a conjugated diene polymer having a high concentration of active terminals tends to be obtained, and a modified conjugated diene polymer having a high modification rate tends to be obtained, which is preferred.
[0306] Polar compounds (polar substances) can be added in the polymerization process. There is a tendency that the aromatic vinyl compound and the conjugated diene compound can be randomly copolymerized, and it can also be used as a vinylating agent for controlling the microstructure of the conjugated diene part. There is also a tendency that the effect is also exerted in the promotion of the polymerization reaction.
[0307] As polar compounds, there can be mentioned, but are not limited to, ethers such as tetrahydrofuran, diethyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol dibutyl ether, dimethoxybenzene, 2,2-bis(2-tetrahydrofuranyl)propane; tertiary amine compounds such as tetramethylethylenediamine, dipiperidylethane, trimethylamine, triethylamine, pyridine, quinuclidine; alkali metal alkoxide compounds such as potassium tert-amylate, potassium tert-butoxide, sodium tert-butoxide, sodium amylate; phosphine compounds such as triphenylphosphine, etc.
[0308] These polar compounds may be used alone or in combination of two or more.
[0309] The amount of the polar compound used is not particularly limited and may be selected depending on the purpose etc., but is preferably 0.01 mol or more and 100 mol or less per 1 mol of the polymerization initiator.
[0310] Such polar compounds (vinylating agents) can be used in appropriate amounts as modifiers of the microstructure of the conjugated diene portion of the polymer, depending on the desired 1,2-vinyl bond amount. Most polar compounds also have an effective randomizing effect in the copolymerization of conjugated diene compounds and aromatic vinyl compounds, and tend to be used as distribution modifiers of aromatic vinyl compounds or modifiers of styrene block amount.
[0311] As a method for randomizing the conjugated diene compound and the aromatic vinyl compound, for example, the following method can be used, as described in Japanese Patent Application Laid-Open No. 59-140211: a copolymerization reaction is initiated using the total amount of styrene and a part of 1,3-butadiene, and the remaining 1,3-butadiene is intermittently added during the copolymerization reaction.
[0312] The polymerization temperature in the polymerization step is preferably a temperature for carrying out living anionic polymerization, and is more preferably 0°C or higher, and further preferably 120°C or lower from the perspective of productivity. By setting the temperature in such a range, there is a tendency to ensure a sufficient amount of the modifier reacted with respect to the active terminal after the polymerization is completed. It is further preferably 50°C or higher and 100°C or lower.
[0313] The step (B) in the method for producing a hydrogenated conjugated diene polymer according to the present embodiment includes a step of adding the branching agent.
[0314] The amount of the branching agent added in the branching step is not particularly limited and can be selected according to the purpose, etc., and is preferably 0.03 mol or more and 0.5 mol or less, more preferably 0.05 mol or more and 0.4 mol or less, and further preferably 0.01 mol or more and 0.25 mol or less, relative to 1 mol of the polymerization initiator. Regarding the timing of adding the branching agent, from the perspective of improving the reproducibility of the polymerization, the monomer conversion rate in the reactor is preferably 50% or more, more preferably 80% or more, and further preferably 90% or more.
[0315] In the step (C) of the method for producing a hydrogenated conjugated diene polymer of the present embodiment, a conjugated diene compound may be added alone, or a conjugated diene compound and an aromatic vinyl compound may be added. The ratio of the amount of monomer components added in the step (A) to the amount of monomer components added in the step (C) (step (A): step (C)) is not particularly limited, but is preferably 99:1 to 5:95, more preferably 95:5 to 30:70, and even more preferably 95:5 to 60:40.
[0316] When the amount of the additional monomer is within the above range, the molecular weight between the branching point based on the branching agent and the branching point based on the coupling agent becomes longer, and there is a tendency to easily obtain a molecular structure with high linearity. By forming a molecular structure with high linearity, the entanglement of molecular chains of the hydrogenated conjugated diene polymer after being made into a sulfide increases, and there is a tendency to obtain a rubber composition with excellent wear resistance, handling stability and breaking strength.
[0317] The step (D) in the method for producing a hydrogenated conjugated diene polymer according to the present embodiment includes a step of adding a coupling agent including the above-mentioned modifier.
[0318] The amount of the coupling agent added is not particularly limited and is preferably selected according to the purpose. It is preferably 0.01 mol to 0.5 mol, more preferably 0.03 mol to 0.4 mol, and further preferably 0.05 mol to 0.25 mol per 1 mol of the active ends of the conjugated diene polymer.
[0319] Regarding the timing of adding the coupling agent, from the viewpoint of improving the reproducibility of polymerization, the monomer conversion rate in the reactor is preferably 50% or more, more preferably 90% or more, and even more preferably 95% or more.
[0320] In the step (E) in the method for producing a hydrogenated conjugated diene polymer according to the present embodiment, a hydrogenation reaction is carried out by the method described in the above-mentioned hydrogenation reaction.
[0321] The hydrogenated conjugated diene polymer of the present embodiment is not particularly limited, and can be a polymer of a conjugated diene compound (monomer) and a branching agent, or a copolymer of a conjugated diene compound, a branching agent and monomers other than them. For example, when the conjugated diene compound is butadiene or isoprene and is polymerized with a branching agent comprising a vinyl aromatic part, the polymer chain is so-called polybutadiene or polyisoprene, and the branched part comprises a polymer of a structure from vinyl aromatics. By having such a structure, there is the following tendency: the linearity of each chain of the polymer chain can be improved and the crosslinking density after vulcanization can be improved, etc., and the effect of improving wear resistance is exerted. Therefore, the hydrogenated conjugated diene polymer of the present embodiment is suitable for tires, resin modification, interior and exterior decoration products of automobiles, shockproof rubber, footwear and other purposes.
[0322] In the method for producing a hydrogenated conjugated diene polymer according to the present embodiment, a deactivator, a neutralizer, and the like may be added to the polymer solution after the coupling step as necessary.
[0323] Examples of the deactivating agent include, but are not limited to, water; alcohols such as methanol, ethanol, and isopropanol; and the like.
[0324] Examples of the neutralizing agent include, but are not limited to, carboxylic acids such as stearic acid, oleic acid, and neodecanoic acid (a mixture of multi-branched carboxylic acids having 9 to 11 carbon atoms, with 10 being the main carbon atoms); aqueous solutions of inorganic acids; and carbon dioxide.
[0325] In the method for producing a hydrogenated conjugated diene polymer according to the present embodiment, it is preferred to add a rubber stabilizer from the viewpoint of preventing gel formation after polymerization and improving stability during processing.
[0326] As the rubber stabilizer, the following known rubber stabilizers may be used but are not limited thereto, for example, preferably antioxidants such as 2,6-di-tert-butyl-4-hydroxytoluene (hereinafter also referred to as "BHT"), 3-(4'-hydroxy-3',5'-di-tert-butylphenol) propionate, and 2-methyl-4,6-bis[(octylthio)methyl]phenol.
[0327] In order to further improve the productivity of the hydrogenated conjugated diene polymer of the present embodiment and the processability when it is made into a composition mixed with a filler and the like, a rubber softener may be added as needed.
[0328] The hydrogenated conjugated diene polymer composition of the present embodiment preferably contains 100 parts by mass of the conjugated diene polymer and 1 to 60 parts by mass of a rubber softener.
[0329] In the hydrogenated conjugated diene polymer composition of the present embodiment, the content of the rubber softener is more preferably 5 to 50 parts by mass, and further preferably 10 to 37.5 parts by mass, based on 100 parts by mass of the conjugated diene polymer.
[0330] The rubber softener is not particularly limited, and examples thereof include extender oil, liquid rubber, and resin.
[0331] As a method for adding a rubber softener to a hydrogenated conjugated diene polymer, a method is preferred but not limited to the following: adding a rubber softener to a hydrogenated conjugated diene polymer solution, mixing to prepare a polymer solution containing a rubber softener, and desolvating the solution.
[0332] Preferred extender oils include, for example, aromatic oils, cycloparaffin oils, and paraffin oils. Among these, from the perspective of environmental safety, prevention of oil seepage, and wet grip properties, alternative aromatic oils having a polycyclic aromatic (PCA) content of 3% by mass or less based on the IP346 method are preferred. Alternative aromatic oils include TDAE (Treated Distillate Aromatic Extracts) and MES (Mild Extraction Solvate) shown in Kautschuk Gummi Kunststoffe 52 (12) 799 (1999), and RAE (Residual Aromatic Extracts).
[0333] Preferred liquid rubbers include, but are not limited to, liquid polybutadiene, liquid styrene-butadiene rubber, and the like.
[0334] As an effect of adding liquid rubber, the processability of the composition prepared by mixing the hydrogenated conjugated diene polymer and the filler can be improved, and the glass transition temperature of the composition can be shifted to the low temperature side, thereby tending to improve the wear resistance, low hysteresis loss and low temperature characteristics of the vulcanized product.
[0335] As preferred resins, there can be cited, but not limited to, aromatic petroleum resins, coumarone-indene resins, terpene resins, rosin derivatives (including tung oil resins), tall oil, derivatives of tall oil, rosin ester resins, natural and synthetic terpene resins, aliphatic hydrocarbon resins, aromatic hydrocarbon resins, mixed aliphatic-aromatic hydrocarbon resins, coumarin-indene resins, phenol resins, p-tert-butylphenol-acetylene resins, phenol-formaldehyde resins, xylene-formaldehyde resins, oligomers of monoolefins, oligomers of dienes, aromatic hydrocarbon resins, aromatic petroleum resins, hydrogenated aromatic hydrocarbon resins, cyclic aliphatic hydrocarbon resins, hydrogenated hydrocarbon resins, hydrocarbon resins, hydrogenated tung oil resins, hydrogenated oil resins, esters of hydrogenated oil resins and monofunctional or polyfunctional alcohols, etc. These resins can be used alone or in combination of two or more. In the case of hydrogenation, all unsaturated groups can be hydrogenated, or a portion can remain.
[0336] The effects of adding the resin include improved processability when the hydrogenated conjugated diene polymer and filler are mixed to form a composition, improved breaking strength after forming a sulfide, and improved wet skid resistance by shifting the glass transition temperature of the composition to a higher temperature.
[0337] The amount of the extender oil, liquid rubber or resin added as a rubber softener is not particularly limited, but is preferably 1 part by mass or more and 60 parts by mass or less, more preferably 5 parts by mass or more and 50 parts by mass or less, and further preferably 10 parts by mass or more and 37.5 parts by mass or less, relative to 100 parts by mass of the hydrogenated conjugated diene polymer of the present embodiment.
[0338] When the rubber softener is added within the above range, the processability when the hydrogenated conjugated diene polymer and the filler are mixed to prepare a composition tends to be good, and the breaking strength and abrasion resistance of the vulcanized product tend to be good.
[0339] (Desolventization process)
[0340] In the method for producing the hydrogenated conjugated diene polymer of the present embodiment, a known method can be used as a method for obtaining the obtained hydrogenated conjugated diene polymer from the polymer solution. The method is not particularly limited, and examples thereof include: a method of obtaining the polymer by filtering out the polymer after separating the solvent by steam stripping, and further dehydrating and drying the polymer; a method of concentrating the polymer by a flash tank, and further devolatilizing the polymer by a venting extruder, etc.; a method of directly devolatilizing the polymer by a rotary dryer, etc.
[0341] (Rubber composition)
[0342] The rubber composition of the present embodiment includes a rubber component and 5.0 parts by mass or more and 150 parts by mass or less of a filler relative to 100 parts by mass of the rubber component.
[0343] Furthermore, the rubber component contains 10 parts by mass or more of the hydrogenated conjugated diene polymer or the hydrogenated conjugated diene polymer composition relative to the total amount (100 parts by mass) of the rubber component in order to improve fuel efficiency, processability and wear resistance.
[0344] In addition, the filler preferably contains a silicon oxide-based inorganic filler.
[0345] The rubber composition of the present embodiment has a silica-based inorganic filler dispersed therein, so that the processability when preparing a vulcanizate tends to be more excellent, and the wear resistance, breaking strength, and balance between low hysteresis loss and wet skid resistance after preparing a vulcanizate tend to be more excellent.
[0346] When the rubber composition of the present embodiment is used for tires, automobile parts such as anti-vibration rubber, and vulcanized rubber applications such as shoes, it is also preferable to contain a silica-based inorganic filler.
[0347] In the rubber composition of the present embodiment, a rubbery polymer other than the hydrogenated conjugated diene polymer (hereinafter simply referred to as “rubbery polymer”) may be used in combination with the hydrogenated conjugated diene polymer.
[0348] Examples of such rubbery polymers include, but are not limited to, conjugated diene polymers or hydrogenated products thereof, random copolymers of conjugated diene compounds and vinyl aromatic compounds or hydrogenated products thereof, block copolymers of conjugated diene compounds and vinyl aromatic compounds or hydrogenated products thereof, non-diene polymers, and natural rubber.
[0349] Specific rubber-like polymers include, but are not limited to, styrene-based elastomers such as butadiene rubber or its hydrogenates, isoprene rubber or its hydrogenates, styrene-butadiene rubber or its hydrogenates, styrene-butadiene block copolymers or their hydrogenates, styrene-isoprene block copolymers or their hydrogenates, and nitrile rubber or its hydrogenates.
[0350] Examples of non-diene polymers include, but are not limited to, olefin elastomers such as ethylene-propylene rubber, ethylene-propylene-diene rubber, ethylene-butene-diene rubber, ethylene-butene rubber, ethylene-hexene rubber, and ethylene-octene rubber, butyl rubber, brominated butyl rubber, acrylic rubber, fluororubber, silicone rubber, chlorinated polyethylene rubber, epichlorohydrin rubber, α,β-unsaturated nitrile-acrylate-conjugated diene copolymer rubber, urethane rubber, and polysulfide rubber.
[0351] Examples of natural rubber include, but are not limited to, RSS No. 3 to No. 5 smoked sheet rubber, SMR, and epoxidized natural rubber.
[0352] The above-mentioned various rubber-like polymers may be modified rubbers to which polar functional groups such as hydroxyl groups and amino groups are added. When used for tire applications, butadiene rubber, isoprene rubber, styrene-butadiene rubber, natural rubber and butyl rubber are preferably used.
[0353] From the aspect of the balance between performance and processing characteristics, the weight average molecular weight of the rubbery polymer is preferably 2000 to 2000000, more preferably 5000 to 1500000. In addition, low molecular weight rubbery polymers, i.e., so-called liquid rubbers, can also be used. These rubbery polymers can be used alone or in combination of two or more.
[0354] When the rubber composition of the present embodiment is made into a rubber composition containing the above-mentioned hydrogenated conjugated diene polymer and a rubbery polymer, the content ratio (mass ratio) of the above-mentioned hydrogenated conjugated diene polymer to the rubbery polymer is preferably 10 / 90 to 100 / 0, more preferably 20 / 80 to 90 / 10, and further preferably 50 / 50 to 80 / 20.
[0355] Therefore, in the rubber component, the hydrogenated conjugated diene polymer is preferably contained in an amount of 10 parts by mass to 100 parts by mass, more preferably 20 parts by mass to 90 parts by mass, and even more preferably 50 parts by mass to 80 parts by mass, relative to the total amount (100 parts by mass) of the rubber component.
[0356] When the content ratio of (the hydrogenated conjugated diene polymer / rubber-like polymer) is within the above range, the sulfide has excellent wear resistance and breaking strength, and the balance between low hysteresis loss and wet skid resistance tends to be satisfactory.
[0357] Examples of fillers included in the rubber composition of the present embodiment include, but are not limited to, silica-based inorganic fillers, carbon black, metal oxides, and metal hydroxides. Among these, silica-based inorganic fillers are preferred.
[0358] The filler may be used alone or in combination of two or more.
[0359] The content of the filler in the rubber composition of the present embodiment is 5.0 to 150 parts by mass, preferably 20 to 100 parts by mass, and more preferably 30 to 90 parts by mass, based on 100 parts by mass of the rubber component containing the hydrogenated conjugated diene polymer.
[0360] In the rubber composition of the present embodiment, the content of the filler is 5.0 parts by mass or more relative to 100 parts by mass of the rubber component from the perspective of expressing the effect of adding the filler, and is 150 parts by mass or less relative to 100 parts by mass of the rubber component from the perspective of sufficiently dispersing the filler and making the processability and mechanical strength of the composition sufficient for practical use.
[0361] The silicon oxide inorganic filler is not particularly limited, and known materials can be used, preferably solid particles containing SiO2 or Si3Al as structural units, and more preferably solid particles containing SiO2 or Si3Al as the main component of the structural unit. Here, the main component refers to a component containing 50% by mass or more, preferably 70% by mass or more, and more preferably 80% by mass or more in the silicon oxide inorganic filler.
[0362] As specific silicon oxide-based inorganic fillers, inorganic fibrous materials such as silicon oxide, clay, talc, mica, diatomaceous earth, wollastonite, montmorillonite, zeolite, and glass fiber can be cited, but not limited to. In addition, a silicon oxide-based inorganic filler, a mixture of a silicon oxide-based inorganic filler and an inorganic filler other than silicon oxide-based inorganic fillers whose surfaces have been hydrophobized can also be cited. Among these, silicon oxide and glass fiber are preferred from aspects such as strength and wear resistance, and silicon oxide is more preferred. As silicon oxide, for example, dry silicon oxide, wet silicon oxide, and synthetic silicate silicon oxide can be cited. Among these silicon oxides, wet silicon oxide is preferred from the aspect of the excellent balance between the improvement effect of the breaking strength and the anti-wet skid resistance.
[0363] From the viewpoint of obtaining practically good wear resistance and breaking strength of the rubber composition, the nitrogen adsorption specific surface area of the silica-based inorganic filler determined by the BET adsorption method is preferably 100 m 2 / g above 300m 2 / g or less, more preferably 170m 2 / g above 250m 2 / g or less. In addition, the specific surface area can be relatively small (for example, the specific surface area is 200m 2 / g or less) and a silicon oxide-based inorganic filler with a relatively large specific surface area (e.g., 200 m 2 / g or more) of a silicon oxide-based inorganic filler. In this embodiment, in particular, when using a relatively large specific surface area (e.g., 200 m 2 In the case of a silicon oxide-based inorganic filler of 0.1% to 0.1% (wt. / g or more), the dispersibility of silicon oxide in the composition containing the above-mentioned hydrogenated conjugated diene polymer is improved, which has an effect of improving wear resistance in particular, and tends to be able to achieve a high balance between good breaking strength and low hysteresis loss.
[0364] The content of the silica-based inorganic filler in the rubber composition is preferably 5.0 to 150 parts by mass, and more preferably 20 to 100 parts by mass, relative to 100 parts by mass of the rubber component containing the hydrogenated conjugated diene polymer. In the rubber composition of the present embodiment, the content of the silica-based inorganic filler is 5.0 parts by mass or more relative to 100 parts by mass of the rubber component from the perspective of showing the effect of adding the inorganic filler, and the content of the silica-based inorganic filler is 150 parts by mass or less relative to 100 parts by mass of the rubber component from the perspective of fully dispersing the inorganic filler and making the processability and mechanical strength of the composition sufficient in practical use.
[0365] Examples of carbon black include, but are not limited to, various grades of carbon black such as SRF, FEF, HAF, ISAF, and SAF. Among these, carbon black having a nitrogen adsorption specific surface area of 50 m 2 / g or more and a dibutyl phthalate (DBP) oil absorption of 80mL / 100g or less.
[0366] In the rubber composition of the present embodiment, the content of carbon black is preferably 0.5 parts by mass or more and 100 parts by mass or less, more preferably 3.0 parts by mass or more and 100 parts by mass or less, and further preferably 5.0 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass of the rubber component containing the hydrogenated conjugated diene polymer, 100 parts by mass. In the rubber composition of the present embodiment, the content of carbon black is preferably 0.5 parts by mass or more relative to 100 parts by mass of the rubber component from the perspective of exhibiting the performance required in applications such as tires, such as dry grip performance and conductivity, and is preferably 100 parts by mass or less relative to 100 parts by mass of the rubber component from the perspective of dispersibility.
[0367] Metal oxides are those with the chemical formula M x O y (M represents a metal atom, and x and y each independently represent an integer of 1 to 6) solid particles as a main component of the structural unit.
[0368] Examples of the metal oxide include, but are not limited to, aluminum oxide, titanium oxide, magnesium oxide, and zinc oxide.
[0369] Examples of the metal hydroxide include, but are not limited to, aluminum hydroxide, magnesium hydroxide, and zirconium hydroxide.
[0370] The rubber composition of the present embodiment may include a silane coupling agent. The silane coupling agent has the function of making the interaction between the rubber component and the inorganic filler close, and preferably has a group having affinity or binding properties for the rubber component and the silica-based inorganic filler, respectively, and a compound having a sulfur bonding portion and an alkoxysilyl or silanol portion in one molecule. Such a compound is not particularly limited, and examples thereof include bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and bis-[2-(triethoxysilyl)-ethyl]-tetrasulfide.
[0371] In the rubber composition of the present embodiment, the content of the silane coupling agent is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 1.0 to 15 parts by mass, relative to 100 parts by mass of the inorganic filler. When the content of the silane coupling agent is within the above range, there is a tendency that the above-mentioned addition effect of the silane coupling agent can be made more significant.
[0372] The rubber composition of the present embodiment may contain a rubber softener from the viewpoint of improving its processability.
[0373] The amount of the rubber softener added is expressed as the total amount of the rubber softener previously contained in the hydrogenated conjugated diene polymer and other rubbery polymers, and added when the rubber composition is prepared, relative to 100 parts by mass of the rubber component containing the hydrogenated conjugated diene polymer.
[0374] As the rubber softener, extender oil, liquid rubber, and resin are suitable.
[0375] The mineral oil-based rubber softener called process oil or extender oil used to soften, increase volume and improve processability of rubber is a mixture of aromatic rings, cycloalkane rings and paraffin chains. The substances whose carbon atoms of paraffin chains account for more than 50% of all carbons are called paraffin series, the substances whose carbon atoms of cycloalkane rings account for more than 30% and less than 45% of all carbons are called cycloalkane series, and the substances whose aromatic carbon atoms account for more than 30% of all carbons are called aromatic series. In the case where the hydrogenated conjugated diene polymer of the present embodiment is a copolymer of a conjugated diene compound and a vinyl aromatic compound, it is preferred that the rubber softener used has a moderate aromatic content because its affinity with the copolymer is good.
[0376] In the rubber composition of the present embodiment, the content of the rubber softener is preferably 0 to 100 parts by mass, more preferably 10 to 90 parts by mass, and further preferably 30 to 90 parts by mass, relative to 100 parts by mass of the rubber component. When the content of the rubber softener is 100 parts by mass or less relative to 100 parts by mass of the rubber component, there is a tendency to suppress bleeding and suppress stickiness on the surface of the rubber composition.
[0377] Regarding the method of mixing hydrogenated conjugated diene polymers with other rubber-like polymers, silicon oxide-based inorganic fillers, carbon black or other fillers, silane coupling agents, rubber softeners and other additives, it is possible to cite but not limited to the melt mixing method using common mixers such as open mills, Banbury mixers, kneaders, single screw extruders, twin screw extruders, multi-screw extruders, etc., and the method of heating and removing the solvent after each component is dissolved and mixed. Among these, from the aspect of productivity and good kneadability, the melt mixing method performed by rollers, Banbury mixers, kneaders, and extruders is preferably used. In addition, any one of the methods of mixing the rubber component with other fillers, silane coupling agents and additives at one time and mixing them several times can also be applied.
[0378] The rubber composition of the present embodiment can be made into a vulcanized composition by vulcanization treatment with a vulcanizing agent. As the vulcanizing agent, free radical initiators such as organic peroxides and azo compounds, oxime compounds, nitroso compounds, polyamine compounds, sulfur, and sulfur-containing compounds can be cited but are not limited to them. Sulfur-containing compounds include sulfur monochloride, sulfur dichloride, disulfide compounds, high molecular weight polysulfide compounds, etc. In the rubber composition of the present embodiment, the content of the vulcanizing agent is preferably 0.01 mass parts to 20 mass parts, more preferably 0.1 mass parts to 15 mass parts, relative to 100 mass parts of the rubber component. As a vulcanization method, an existing known method can be applied, and the vulcanization temperature is preferably 120°C to 200°C, more preferably 140°C to 180°C.
[0379] During vulcanization, a vulcanization accelerator can be used as required. As a vulcanization accelerator, existing known materials can be used, and examples thereof include but are not limited to sulfonamide, guanidine, thiuram, aldehyde-amine, aldehyde-ammonia, thiazole, thiourea, and dithiocarbamate vulcanization accelerators. In addition, as a vulcanization aid, examples thereof include but are not limited to zinc white and stearic acid. The content of the vulcanization accelerator is preferably 0.01 mass parts or more and 20 mass parts or less, and more preferably 0.1 mass parts or more and 15 mass parts or less relative to 100 mass parts of the rubber component.
[0380] In the rubber composition of the present embodiment, various additives such as other softeners and fillers other than the above, heat stabilizers, antistatic agents, weather stabilizers, anti-aging agents, colorants, lubricants, etc. can be used within the scope that does not harm the purpose of the present embodiment. As other softeners, known softeners can be used. As other fillers, there is no particular limitation, and specifically, calcium carbonate, magnesium carbonate, aluminum sulfate, and barium sulfate can be cited. As the above-mentioned heat stabilizers, antistatic agents, weather stabilizers, anti-aging agents, colorants, and lubricants, known materials can be used respectively.
[0381] The rubber composition of the present embodiment is suitable as a rubber composition for a tire. That is, the tire of the present embodiment is formed using the rubber composition.
[0382] The rubber composition for tires can be applied to various parts of tires such as treads, tire carcasses, bead, and bead portions of various tires such as fuel-saving tires, all-season tires, high-performance tires, and studless tires, but is not limited thereto. In particular, the rubber composition for tires has excellent wear resistance, breaking strength, and a balance between low hysteresis loss and wet skid resistance after being made into a vulcanized material, and is therefore suitable for use as a tread for fuel-saving tires and high-performance tires.
[0383] Example
[0384] The present embodiment will be described in more detail below with reference to specific examples and comparative examples, but the present embodiment is not limited to the following examples and comparative examples.
[0385] Various physical properties in Examples and Comparative Examples were measured by the methods shown below.
[0386] (Polymer Mooney viscosity)
[0387] The Mooney viscosity of a conjugated diene polymer or a hydrogenated conjugated diene polymer as a sample was measured using a Mooney viscometer (trade name "VR1132" manufactured by Ueshima Seisakusho Co., Ltd.) in accordance with ISO 289 with an L-shaped rotor.
[0388] The measurement temperature was set to 100° C. when a hydrogenated conjugated diene polymer was used as a sample.
[0389] Specifically, the sample was first preheated at the test temperature for 1 minute, and then the rotor was rotated at 2 rpm. The torque of the sample was measured 4 minutes later, and the measured value was taken as the Mooney viscosity (ML (1+4) ).
[0390] (Degree of branching (Bn))
[0391] The degree of branching (Bn) is measured by GPC-light scattering method with a viscosity detector using a conjugated diene polymer or hydrogenated conjugated diene polymer containing no rubber softener as a sample. The measurement is performed using a gel permeation chromatography (GPC) measuring apparatus (trade name "GPCmax VE-2001" manufactured by Malvern) to which three columns using polystyrene gel as a filler are connected, and three detectors connected in order: a light scattering detector, a differential refractive index (RI) detector, and a viscosity detector (trade name "TDA305" manufactured by Malvern) are used. The absolute molecular weight of the sample is obtained from the results of the light scattering detector and the RI detector, and the intrinsic viscosity of the sample is obtained from the results of the RI detector and the viscosity detector based on standard polystyrene.
[0392] Assume that the linear polymer follows the intrinsic viscosity [η] = -3.883M 0.771 The shrinkage factor (g') was calculated as the ratio of the intrinsic viscosity corresponding to each molecular weight by applying the above formula. It should be noted that in this formula, M represents the absolute molecular weight.
[0393] Thereafter, the obtained shrinkage factor (g') was used to calculate the degree of branching (Bn) defined as g' = 6Bn / {(Bn+1)(Bn+2)}.
[0394] Tetrahydrofuran (hereinafter also referred to as "THF") added with 5 mmol / L of triethylamine was used as the eluent.
[0395] As columns, trade names "TSKgel G4000HXL", "TSKgel G5000HXL" and "TSKgel G6000HXL" manufactured by Tosoh Corporation were connected and used.
[0396] 20 mg of a sample for measurement was dissolved in 10 mL of THF to prepare a measurement solution. 100 μL of the measurement solution was injected into a GPC measurement device and measurement was performed under the conditions of an oven temperature of 40° C. and a THF flow rate of 1 mL / min.
[0397] (Weight average molecular weight, component with a molecular weight of 300,000 or less (component LM))
[0398] Measurement condition 1: Using a conjugated diene polymer or a hydrogenated conjugated diene polymer as a sample, a GPC measuring apparatus (trade name "HLC-8320GPC" manufactured by Tosoh Corporation) connected to three columns using polystyrene gel as a filler is used, and a chromatogram is measured using an RI detector (trade name "HLC8020" manufactured by Tosoh Corporation), and the weight average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn) and components with a molecular weight of less than 300,000 (component LM) of the sample are calculated based on a calibration curve obtained using standard polystyrene.
[0399] THF (tetrahydrofuran) containing 5 mmol / L triethylamine was used as the eluent. Three columns of "TSKgel SuperMultiporeHZ-H" manufactured by Tosoh Corporation were connected, and a "TSKguardcolumn SuperMP(HZ)-H" manufactured by Tosoh Corporation was connected to the front of the column as a guard column.
[0400] 10 mg of a measurement sample was dissolved in 10 mL of THF to prepare a measurement solution, 10 μL of the measurement solution was injected into a GPC measurement device, and measurement was performed under the conditions of an oven temperature of 40° C. and a THF flow rate of 0.35 mL / min.
[0401] Among the various samples measured under the above measurement condition 1, the samples with a molecular weight distribution (Mw / Mn) value of less than 1.6 were measured under the following measurement condition 2. The samples whose molecular weight distribution value was 1.6 or more when measured under measurement condition 1 were measured under measurement condition 1.
[0402] Measurement condition 2: Using a conjugated diene polymer or a hydrogenated conjugated diene polymer as a sample, a chromatogram is measured using a GPC measuring apparatus connected to three columns using polystyrene gel as a filler, and based on a calibration curve obtained using standard polystyrene, the weight average molecular weight (Mw), number average molecular weight (Mn) and the component with a molecular weight of less than 300,000 (component LM) of the sample are determined.
[0403] THF to which 5 mmol / L triethylamine was added was used as the eluent. For the column, a guard column with the trade name "TSKguardcolumn SuperH-H" manufactured by Tosoh Corporation was used, and a column with the trade names "TSKgel SuperH5000", "TSKgel SuperH6000" and "TSKgel SuperH7000" manufactured by Tosoh Corporation was used.
[0404] An RI detector (trade name "HLC8020" manufactured by Tosoh Corporation) was used at an oven temperature of 40°C and a THF flow rate of 0.6 mL / min. 10 mg of a sample for measurement was dissolved in 20 mL of THF to prepare a measurement solution, and 20 μL of the measurement solution was injected into the GPC measurement apparatus for measurement.
[0405] (Modification rate)
[0406] The modification rate of a conjugated diene polymer or a hydrogenated conjugated diene polymer containing no rubber softener is measured as a sample by column adsorption GPC method as follows, using the property that the modified basic polymer component is adsorbed on a GPC column filled with silica gel.
[0407] The adsorption amount on the silica column was determined from the difference between the chromatogram obtained by measuring a sample solution containing the sample and low molecular weight internal standard polystyrene using a polystyrene column and the chromatogram obtained by measuring a silica column, and the polymer modification rate was obtained.
[0408] Specifically, as shown below. In addition, for samples whose molecular weight distribution value is 1.6 or more in the measurement performed using the above-mentioned measurement condition 1 (weight average molecular weight), the measurement is performed using the following measurement condition 3; for samples whose molecular weight distribution value is less than 1.6, the measurement is performed using the following measurement condition 4.
[0409] Preparation of sample solution: 10 mg of the sample and 5 mg of standard polystyrene were dissolved in 20 mL of THF to prepare a sample solution.
[0410] Measurement condition 3: GPC measurement conditions using a polystyrene column:
[0411] The HLC-8320GPC manufactured by Tosoh Corporation was used, THF with 5 mmol / L triethylamine added was used as the eluent, 10 μL of the sample solution was injected into the device, and a chromatogram was obtained using an RI detector under the conditions of a column box temperature of 40°C and a THF flow rate of 0.35 mL / min. As for the column, three TSKgelSuperMultiporeHZ-H manufactured by Tosoh Corporation were connected, and a TSKguard column SuperMP(HZ)-H manufactured by Tosoh Corporation was connected to the front section as a guard column for use.
[0412] Measurement condition 4: THF with 5 mmol / L triethylamine added was used as the eluent, and 20 μL of the sample solution was injected into the device for measurement. As for the column, the protective column used the trade name "TSK guard column SuperH-H" manufactured by Tosoh Corporation, and the column used the trade name "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgelSuperH7000" manufactured by Tosoh Corporation. The chromatogram was obtained by using an RI detector (HLC8020 manufactured by Tosoh Corporation) at a column box temperature of 40°C and a THF flow rate of 0.6 mL / min.
[0413] GPC measurement conditions using silica columns: Use the product name "HLC-8320GPC" manufactured by Tosoh Corporation, use THF as the eluent, inject 50 μL of the sample solution into the device, and use the RI detector to obtain a chromatogram under the conditions of a column box temperature of 40°C and a THF flow rate of 0.5 ml / min. As for the column, the product names "Zorbax PSM-1000S", "PSM-300S", and "PSM-60S" were connected and used, and the product name "DIOL4.6×12.5mm5micron" was connected to the front section as a protective column.
[0414] Calculation method of polymer modification rate: Let the peak area of the chromatogram using a polystyrene column as 100, let the peak area of the sample be P1, and the peak area of the standard polystyrene be P2. Also, let the peak area of the chromatogram using a silica column as 100, let the peak area of the sample be P3, and the peak area of the standard polystyrene be P4. Based on P1 to P4, the polymer modification rate (%) is calculated by the following formula.
[0415] Modification rate (%) = [1-(P2×P3) / (P1×P4)]×100
[0416] (where P1+P2=P3+P4=100)
[0417] (Molecular weight (absolute molecular weight) measured by GPC-light scattering method)
[0418] A conjugated diene polymer or a hydrogenated conjugated diene polymer that does not contain a rubber softener is used as a sample, and a chromatogram is measured using a GPC-light scattering measuring device connected to three columns using polystyrene gel as a filler, and the weight average molecular weight (Mw-i) (also called "absolute molecular weight") is calculated based on solution viscosity and a light scattering method.
[0419] As the eluent, a mixed solution of tetrahydrofuran and triethylamine (THF in TEA: prepared by mixing 5 mL of triethylamine with 1 L of tetrahydrofuran) was used.
[0420] As the column, a guard column: trade name "TSK guard column HHR-H" manufactured by Tosoh Corporation and a column: trade name "TSKgel G6000HHR", "TSKgel G5000HHR" and "TSKgel G4000HHR" manufactured by Tosoh Corporation were connected and used.
[0421] A GPC-light scattering measuring apparatus (trade name "Viscotek TDAmax" manufactured by Malvern) was used at an oven temperature of 40°C and a THF flow rate of 1.0 mL / min. 10 mg of a sample for measurement was dissolved in 20 mL of THF to prepare a measurement solution, and 200 μL of the measurement solution was injected into the GPC measuring apparatus for measurement.
[0422] (Combined styrene content, hydrogenation rate, mathematical formula (S), mathematical formula (T))
[0423] A conjugated diene polymer or a hydrogenated conjugated diene polymer not containing a rubber softener was used as a sample, and the amount of bound styrene in the polymer, the structural unit represented by the above formula (1), the structural unit represented by the above formula (2), the structural unit represented by the above formula (3), and the structural unit represented by the above formula (4) were measured. In order to calculate the hydrogenation rate of the double bonds of the structural unit derived from 1,3-butadiene (hereinafter also referred to as "hydrogenation rate"), the value of the above mathematical formula (S) and the value of the above mathematical formula (T), a nuclear magnetic resonance apparatus ( 1 H-NMR) was measured under the following conditions. 1 The conditions for H-NMR measurement are as follows.
[0424] (Measurement conditions)
[0425] Measuring equipment: JNM-LA400 (manufactured by JEOL)
[0426] Solvent: deuterated chloroform
[0427] Measurement samples: Extracts of polymers before and after hydrogenation
[0428] Sample concentration: 50 mg / mL
[0429] Observation frequency: 400MHz
[0430] Chemical shift standard: TMS (tetramethylsilane)
[0431] Pulse delay: 2.904 seconds
[0432] Scan times: 64 times
[0433] Pulse width: 45°
[0434] Measurement temperature: 26℃
[0435] (Cold Flow)
[0436] A conjugated diene polymer (composition) or a hydrogenated conjugated diene polymer (composition) was used as a sample for measurement. Regarding cold flow, a load of 1 kg was applied to a sample of 40 mm × 40 mm × thickness (H0) 50 mm at 25°C, and the thickness change rate (%) was calculated from the thickness (H60) after 60 minutes of standing using the following formula.
[0437] Thickness change rate (%) = (H0-H60) × 100 / H0
[0438] Furthermore, regarding Comparative Examples 2 to 5 and Examples 1 to 2, 4 to 5, and Example 31, the result of Comparative Example 1 was set to 100 for indexing. Regarding Examples 6 to 8, the result of Comparative Example 6 was set to 100 for indexing. Regarding Examples 9 to 11, the result of Comparative Example 7 was set to 100 for indexing. The result of Comparative Example 8 was set to 100 for indexing. Regarding Examples 15 to 17, the result of Comparative Example 9 was set to 100 for indexing.
[0439] For Comparative Examples 11 to 12 and Examples 18 to 23, the result of Comparative Example 10 was indexed as 100. For Examples 24 to 26, the result of Comparative Example 13 was indexed as 100. For Examples 27 to 29, the result of Comparative Example 14 was indexed as 100. For Example 30, the result of Comparative Example 15 was indexed as 100. For Examples 32 to 33, the result of Comparative Example 16 was indexed as 100.
[0440] The smaller the index is, the smaller the cold flow of the rubber compact during storage is, and the better the handling property is.
[0441] If the index is 79 or less, it is very good (◎◎ in the table), if the index is 80 to 89, it is good (◎ in the table), if the index is 90 to 99, there is no problem in practical use (○ in the table), if the index is 100 to 105, it is slightly poor (△ in the table), and if the index is 105 or more, there is a problem in practical use (× in the table).
[0442] (Preparation of Hydrogenation Catalyst)
[0443] In the Examples and Comparative Examples described below, the hydrogenation catalyst used in producing the hydrogenated conjugated diene polymer was prepared by the following method.
[0444] A reaction vessel equipped with a stirring device was purged with nitrogen in advance, and 1 L of dried and purified cyclohexane was added thereto. Then, 100 mmol of bis(η5-cyclopentadiene)titanium dichloride was added. While the mixture was fully stirred, a n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was reacted at room temperature for about 3 days. Thus, a hydrogenation catalyst (T) was obtained.
[0445] (Structure of branching agent)
[0446] In the examples and comparative examples described below, trimethoxy(4-vinylphenyl)silane (BS-1) or dimethoxymethyl(4-vinylphenyl)silane (BS-2) was used as a branching agent, and both were monomer units based on the compound represented by the following formula (5).
[0447] The structure of trimethoxy(4-vinylphenyl)silane (BS-1) is as follows: 1 is hydrogen, R 2 ~R 3 is methyl, m is 0, n is 3, and l is 0.
[0448] In addition, the structure of dimethoxymethyl (4-vinylphenyl) silane (BS-2) is: 1 is hydrogen, R 2 ~R 3 is methyl, m is 1, n is 2, and l is 0.
[0449] [Chemistry 10]
[0450]
[0451] (In formula (5), R 1 The group represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and a part of the group may have a branched structure.
[0452] R 2 ~R 3Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of them may have a branched structure.
[0453] When there are multiple R 1 ~R 3 Each one is independent.
[0454] X 1 represents a halogen atom. When there are plural X 1 Each one is independent.
[0455] m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3. (m+n+l) represents 3.)
[0456] (Comparative Example 1) Hydrogenated conjugated diene polymer (Sample B1)
[0457] A temperature-controllable autoclave with an internal volume of 40 L and equipped with a stirrer and a jacket was used as a reactor. 2,220 g of 1,3-butadiene from which impurities had been removed in advance, 780 g of styrene, 21,000 g of cyclohexane, 30 mmol of tetrahydrofuran (THF) as a polar substance, and 15 mmol of 2,2-bis(2-tetrahydrofuryl)propane (BOP) were added to the reactor, and the temperature inside the reactor was maintained at 40°C.
[0458] 18 mmol of n-butyllithium was supplied as a polymerization initiator to the reactor to initiate polymerization.
[0459] After the polymerization reaction started, the temperature in the reactor began to rise due to the heat generated by the polymerization, and the final temperature in the reactor reached 76°C. 2 minutes after reaching the peak of the reaction temperature, 6.0 mmol of N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) was added to the reactor as a coupling agent, and the coupling reaction was carried out for 20 minutes. 3.0 mmol of methanol was added to the polymer solution as a reaction terminator to obtain a solution of a conjugated diene polymer.
[0460] Furthermore, the above-prepared hydrogenation catalyst (T) was added to the obtained conjugated diene polymer solution in an amount of 60 ppm based on Ti relative to 100 parts by mass of the conjugated diene polymer, and a hydrogenation reaction was carried out for 1 hour under the conditions of a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. to obtain a hydrogenated conjugated diene polymer solution. The hydrogenation rate of the structural unit derived from butadiene in the obtained hydrogenated conjugated diene polymer was 60.0%.
[0461] To the obtained hydrogenated conjugated diene polymer solution, 12.6 g of n-octadecyl 3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol were added as antioxidants, and then the solvent was removed by steam stripping, and the mixture was dried in a dryer to obtain a hydrogenated conjugated diene polymer (Sample B1).
[0462] Sample B1 was analyzed and the results are shown in Table 1-1.
[0463] From the measurement results, it is understood that the structure of the conjugated diene polymer before the addition of the coupling agent in the sample B1 has a linear polymer structure and does not have a star-shaped polymer.
[0464] (Comparative Example 2) Conjugated diene polymer (Sample B2)
[0465] A temperature-controllable autoclave having an internal volume of 40 L and equipped with a stirrer and a jacket was used as a reactor. 1,887 g of 1,3-butadiene (initial butadiene) from which impurities had been removed in advance, 780 g of styrene, 21,000 g of cyclohexane, 30 mmol of tetrahydrofuran (THF) as a polar substance, and 69 mmol of 2,2-bis(2-tetrahydrofuryl)propane (BOP) were added to the reactor, and the temperature inside the reactor was maintained at 42°C.
[0466] 92 mmol of n-butyllithium was supplied as a polymerization initiator to the reactor to initiate polymerization.
[0467] After the polymerization reaction started, the temperature in the reactor began to rise due to the heat generated by the polymerization. When the monomer conversion rate in the reactor reached 98%, 18 mmol of trimethoxy (4-vinylphenyl) silane (BS-1) was added as a branching agent and stirred for 5 minutes. After that, 333 g of 1,3-butadiene (additional butadiene) was added and reacted. The final temperature in the reactor was 75°C.
[0468] The final temperature in the reactor reached 76°C. 2 minutes after reaching the peak of the reaction temperature, 8.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2) was added to the reactor as a coupling agent, and a coupling reaction was carried out for 20 minutes. 5.7 mmol of methanol was added to the polymer solution as a reaction terminator to obtain a solution of a conjugated diene polymer.
[0469] To the obtained conjugated diene polymer solution, 12.6 g of n-octadecyl 3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol were added as antioxidants, and then the solvent was removed by steam stripping, and the mixture was dried in a dryer to obtain a conjugated diene polymer (sample B2).
[0470] Sample B2 was analyzed and the results are shown in Table 1-1.
[0471] It should be noted that, regarding the polymer before the branching agent is added, the polymer after the branching agent is added, and the polymer in each process after the coupling agent is added, the structure of the coupled conjugated diene polymer is identified by comparing the molecular weight determined based on GPC with the degree of branching determined based on GPC with a viscometer. The structure of each sample is identified in the same manner below. From the results of the measurement, it can be seen that regarding the structure of sample B2, the conjugated diene polymer after the branching agent is added has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymer after the coupling agent is added has a portion of a vinyl monomer containing an alkoxysilyl group in an average of 2 branched chains of the star-shaped structure.
[0472] (Comparative Example 3) Hydrogenated conjugated diene polymer (Sample B3)
[0473] A temperature-controllable autoclave having an internal volume of 40 L and equipped with a stirrer and a jacket was used as a reactor. 1,887 g of 1,3-butadiene (initial butadiene) from which impurities had been removed in advance, 780 g of styrene, 21,000 g of cyclohexane, 30 mmol of tetrahydrofuran (THF) as a polar substance, and 69 mmol of 2,2-bis(2-tetrahydrofuryl)propane (BOP) were added to the reactor, and the temperature inside the reactor was maintained at 42°C.
[0474] 92 mmol of n-butyllithium was supplied as a polymerization initiator to the reactor to initiate polymerization.
[0475] After the polymerization reaction started, the temperature in the reactor began to rise due to the heat generated by the polymerization. When the monomer conversion rate in the reactor reached 98%, 18 mmol of trimethoxy (4-vinylphenyl) silane (BS-1) was added as a branching agent and stirred for 5 minutes. After that, 333 g of 1,3-butadiene (additional butadiene) was added and reacted. The final temperature in the reactor was 75°C.
[0476] The final temperature in the reactor reached 76°C. 2 minutes after reaching the peak of the reaction temperature, 8.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2) was added to the reactor as a coupling agent, and a coupling reaction was carried out for 20 minutes. 5.7 mmol of methanol was added to the polymer solution as a reaction terminator to obtain a solution of a conjugated diene polymer.
[0477] To the obtained conjugated diene polymer solution, 60 ppm of the above-prepared hydrogenation catalyst (T) was added based on Ti relative to 100 parts by mass of the conjugated diene polymer, and a hydrogenation reaction was carried out for 30 minutes under the conditions of a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. to obtain a hydrogenated conjugated diene polymer solution. The hydrogenation rate of the structural unit derived from butadiene in the obtained hydrogenated conjugated diene polymer was 20.0%.
[0478] To the obtained hydrogenated conjugated diene polymer solution, 12.6 g of 3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionic acid n-octadecyl ester and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol were added as antioxidants, and then the solvent was removed by steam stripping, and dried in a dryer to obtain a hydrogenated conjugated diene polymer (sample B3). The hydrogenation rate of sample B3 was 20%.
[0479] Sample B3 was analyzed and the results are shown in Table 1-1.
[0480] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in sample B3 has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymer after adding the coupling agent has a moiety derived from a vinyl monomer containing an alkoxysilyl group in an average of 2 branches of the star structure.
[0481] (Examples 1, 2, Comparative Example 4) Hydrogenated conjugated diene polymers (samples B4, B5, B6, respectively)
[0482] Hydrogenated conjugated diene polymers (Sample B4, Sample B5, Sample B6) were obtained by the same operation as Comparative Example 3 except adjusting the cumulative flow rate of hydrogen in the hydrogenation reaction (hydrogenation reaction). The hydrogenation rates of Sample B4, Sample B5, and Sample B6 were 63.0%, 92.0%, and 99.5%, respectively.
[0483] Sample B4, Sample B5, and Sample B6 were analyzed, and the results are shown in Table 1-1.
[0484] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in samples B4, B5 and B6 has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 2 branches of the star structure.
[0485] (Comparative Example 5) Hydrogenated conjugated diene polymer (Sample B8)
[0486] A hydrogenated conjugated diene polymer (Sample B8) was obtained in the same manner as in Comparative Example 1 except that the amount of 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 19 mmol, the amount of n-butyl lithium as a polymerization initiator was changed to 24 mmol, the amount of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2) as a coupling agent was changed to 4.3 mmol, and the amount of methanol as a reaction terminator was changed to 5.3 mmol. The hydrogenation rate of Sample B8 was 96%.
[0487] Sample B8 was analyzed and the results are shown in Table 1-1.
[0488] From the measurement results, it is found that the structure of the conjugated diene polymer in Sample B8 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0489] (Example 4) Hydrogenated conjugated diene polymer (Sample B9)
[0490] A hydrogenated conjugated diene polymer (Sample B9) was obtained by the same operation as in Comparative Example 3 except that the coupling agent was changed to 4.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2) and 4.0 mmol of silicon tetrachloride (Compound 3) and the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rate of Sample B9 was 65%.
[0491] Sample B9 was analyzed and the results are shown in Table 1-1.
[0492] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in sample B9 has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from the vinyl monomer containing an alkoxysilyl group in an average of 2 branches of the star structure.
[0493] (Example 5) Hydrogenated conjugated diene polymer (Sample B10)
[0494] A hydrogenated conjugated diene polymer (Sample B10) was obtained by the same operation as in Comparative Example 3 except that 18 mmol of trimethoxy(4-vinylphenyl)silane (BS-1) as a branching agent was added when the monomer conversion rate in the reactor was 60%, and 7.4 mmol of trimethoxy(4-vinylphenyl)silane (BS-1) as a branching agent was added when the monomer conversion rate in the reactor was 98%, 9.8 mmol of 1,3-dimethyl-2-imidazolidinone (Compound 4) as a modifier was used instead of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2) as a coupling agent, 5.3 mmol of methanol as a reaction terminator, and the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rate of Sample B10 was 65%.
[0495] Sample B10 was analyzed and the results are shown in Table 1-1.
[0496] From the measurement results, it was found that regarding the structure of sample B10, the conjugated diene polymer after the second addition of the branching agent had a star-shaped polymer structure with an average of 5.2 branches and had a portion derived from a vinyl monomer containing an alkoxysilyl group.
[0497] (Comparative Example 6) Hydrogenated conjugated diene polymer (Sample B11)
[0498] A hydrogenated conjugated diene polymer (Sample B11) was obtained by the same operation as Comparative Example 1 except that the initial butadiene was changed to 2,700 g, the styrene was changed to 300 g, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 4.8 mmol, the n-butyl lithium as a polymerization initiator was changed to 22 mmol, the N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was changed to 7.3 mmol, and the methanol as a reaction terminator was changed to 3.3 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rate of Sample B11 was 60%.
[0499] Sample B11 was analyzed and the results are shown in Table 1-2.
[0500] From the measurement results, it is found that the structure of the conjugated diene polymer in sample B11 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0501] (Examples 6, 7, and 8) Hydrogenated conjugated diene polymers (samples B12, B13, and B14, respectively)
[0502] Hydrogenated conjugated diene polymers (Sample B12, Sample B13, and Sample B14) were obtained by the same operation as in Comparative Example 3 except that the initial butadiene was changed to 2,295 g, the styrene was changed to 300 g, the additional butadiene was changed to 405 g, the polar substance 2,2-bis(2-tetrahydrofuryl)propane (BOP) was changed to 21 mmol, the polymerization initiator n-butyl lithium was changed to 110 mmol, the branching agent was changed to 35 mmol of dimethoxymethyl(4-vinylphenyl)silane (BS-2), the coupling agent was changed to 5.9 mmol of N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5), and the reaction terminator was changed to 8.6 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rates of Sample B12, Sample B13, and Sample B14 were 60.0%, 88.0%, and 93.0%, respectively.
[0503] Sample B12, Sample B13, and Sample B14 were analyzed, and the results are shown in Table 1-2.
[0504] The measurement results show that the structure of the conjugated diene polymers in samples B12, B13 and B14 before the addition of the coupling agent has a star-shaped polymer structure with an average of 3.0 branches, and the conjugated diene polymers after the addition of the coupling agent have a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 4 branches of the star structure.
[0505] (Comparative Example 7) Hydrogenated conjugated diene polymer (Sample B15)
[0506] A hydrogenated conjugated diene polymer (Sample B15) was obtained by the same operation as in Comparative Example 1 except that the initial butadiene was changed to 1,950 g, the styrene was changed to 1,050 g, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 2.1 mmol, the n-butyl lithium as a polymerization initiator was changed to 19 mmol, the N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was changed to 6.3 mmol, and the methanol as a reaction terminator was changed to 2.9 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rate of Sample B15 was 50%.
[0507] Sample B15 was analyzed and the results are shown in Table 1-3.
[0508] From the measurement results, it is found that the structure of the conjugated diene polymer in sample B15 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0509] (Examples 9, 10, 11) Hydrogenated conjugated diene polymers (samples B16, B17, B18, respectively)
[0510] Hydrogenated conjugated diene polymers (Sample B16, Sample B17, and Sample B18) were obtained by the same operation as in Comparative Example 3 except that the initial butadiene was changed to 1,560 g, the styrene was changed to 1,050 g, the additional butadiene was changed to 390 g, the polar substance 2,2-bis(2-tetrahydrofuryl)propane (BOP) was changed to 12 mmol, the polymerization initiator n-butyl lithium was changed to 146 mmol, the branching agent trimethoxy(4-vinylphenyl)silane (BS-1) was changed to 30 mmol, the coupling agent was changed to 7.2 mmol of N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5), the reaction terminator methanol was changed to 0 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rates of Sample B16, Sample B17, and Sample B18 were 39.0%, 64.0%, and 95.0%, respectively.
[0511] Sample B16, Sample B17, and Sample B18 were analyzed, and the results are shown in Table 1-3.
[0512] The measurement results show that the structure of the conjugated diene polymers in samples B16, B17 and B18 before the addition of the coupling agent has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymers after the addition of the coupling agent have a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 4 branches of the star structure.
[0513] (Comparative Example 8) Hydrogenated conjugated diene polymer (Sample B19)
[0514] A hydrogenated conjugated diene polymer (Sample B19) was obtained by the same operation as in Comparative Example 1 except that the initial butadiene was changed to 2,220 g, the styrene was changed to 780 g, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 5.5 mmol, the n-butyl lithium as a polymerization initiator was changed to 19 mmol, the N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was changed to 6.3 mmol, and the methanol as a reaction terminator was changed to 2.9 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rate of Sample B19 was 70%.
[0515] Sample B19 was analyzed and the results are shown in Table 1-4.
[0516] From the measurement results, it is found that the structure of the conjugated diene polymer in sample B19 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0517] (Comparative Example 9) Hydrogenated conjugated diene polymer (Sample B23)
[0518] A hydrogenated conjugated diene polymer (Sample B23) was obtained by the same operation as in Comparative Example 1 except that the initial butadiene was changed to 3,000 g, styrene was changed to 0 g, 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 4.3 mmol, n-butyl lithium as a polymerization initiator was changed to 21 mmol, N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was changed to 6.9 mmol, methanol as a reaction terminator was changed to 3.2 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rate of Sample B23 was 60%.
[0519] Sample B23 was analyzed and the results are shown in Table 1-5.
[0520] From the measurement results, it is found that the structure of the conjugated diene polymer in sample B23 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0521] (Examples 15, 16, 17) Hydrogenated conjugated diene polymers (samples B24, B25, B26, respectively)
[0522] Hydrogenated conjugated diene polymers (Sample B24, Sample B25, and Sample B26) were obtained by the same operation as Comparative Example 1 except that the initial butadiene was changed to 3,000 g, styrene was changed to 0 g, 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 6.8 mmol, n-butyl lithium as a polymerization initiator was changed to 45 mmol, N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5) as a coupling agent was changed to 4.5 mmol, and methanol as a reaction terminator was changed to 6.9 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rates of Sample B24, Sample B25, and Sample B26 were 60%, 75%, and 94%, respectively.
[0523] Sample B24, Sample B25, and Sample B26 were analyzed, and the results are shown in Table 1-5.
[0524] The measurement results show that the structure of the conjugated diene polymer before the addition of the coupling agent in samples B24, B25, and B26 has a linear polymer structure and does not have a star-shaped polymer.
[0525] (Example 31) Hydrogenated conjugated diene polymer (Sample B27)
[0526] A hydrogenated conjugated diene polymer (Sample B27) was obtained by the same operation as in Comparative Example 3 except that the initial butadiene was changed to 1,887 g, the styrene was changed to 780 g, the additional butadiene was changed to 333 g, the polar substance 2,2-bis(2-tetrahydrofuryl)propane (BOP) was changed to 72 mmol, the polymerization initiator n-butyl lithium was changed to 98 mmol, the branching agent trimethoxy(4-vinylphenyl)silane (BS-1) was changed to 22.6 mmol, the coupling agent 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2) was changed to 4.9 mmol, the reaction terminator methanol was changed to 3.7 mmol, and the cumulative flow rate of hydrogen was adjusted. The hydrogenation rate of Sample B27 was 71.0%.
[0527] Sample B27 was analyzed and the results are shown in Table 1-5.
[0528] The measurement results show that the structure of the conjugated diene polymer in sample B27 before adding the coupling agent has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 3 branches of the star structure.
[0529]
[0530] [Table 1-2]
[0531]
[0532] [Table 1-3]
[0533]
[0534] [Table 1-4]
[0535]
[0536] [Table 1-5]
[0537]
[0538] The branching agents and coupling agents described in Tables 1-1 to 1-5 are the following compounds.
[0539] [Branching agent]
[0540] BS-1: Trimethoxy(4-vinylphenyl)silane
[0541] BS-2: Dimethoxymethyl (4-vinylphenyl) silane
[0542] [Coupling agent]
[0543] Compound 1: N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane
[0544] Compound 2: 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane
[0545] Compound 3: Silicon tetrachloride
[0546] Compound 4: 1,3-Dimethyl-2-imidazolidinone
[0547] Compound 5: N,N,N',N'-Tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine
[0548] [Application Examples 1 to 2, 4 to 11, 15 to 17 and Application Comparative Examples 1 to 9, Application Example 33]
[0549] Samples B1 to B6, B8 to B19, B23 to B26, and B27 shown in Tables 1-1 to 1-5 were used as raw rubber components, and rubber compositions containing the raw rubber components were obtained under the blending conditions C shown below.
[0550] (Rubber component)
[0551] Conjugated diene polymer or hydrogenated conjugated diene polymer (samples B1 to B6, B8 to B19, B23 to B26, B27): 100 parts by mass
[0552] (Mixing Condition C)
[0553] The amount of each compounding agent added is expressed in parts by mass relative to 100 parts by mass of the rubber component excluding the rubber softener.
[0554] Silicon oxide 1 (trade name "Ultrasil 700 0GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m2 / g): 50.0 parts by mass
[0555] Silicon oxide 2 (trade name "Zeosil Premium 2 00MP" manufactured by Rhodia, nitrogen adsorption specific surface area 220 m2 / g): 25.0 parts by mass
[0556] Carbon black (trade name "SEAST KH (N339)" manufactured by Tokai Tanso Co., Ltd.): 5.0 parts by mass
[0557] Silane coupling agent (trade name "Si75" manufactured by Evonik Degussa, bis(triethoxysilylpropyl) disulfide): 6.0 parts by mass
[0558] SRAE oil (trade name "Process NC140" manufactured by JX Nippon Oil & Energy Corporation): 25.0 parts by mass
[0559] Zinc white: 2.5 parts by mass
[0560] Stearic acid: 1.0 parts by mass
[0561] Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine): 2.0 parts by mass
[0562] Sulfur: 2.2 parts by mass
[0563] Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazolylsulfenamide): 1.7 parts by mass
[0564] Vulcanization accelerator 2 (diphenylguanidine): 2.0 parts by mass
[0565] Total: 222.4 parts by mass
[0566] (Mixing method)
[0567] The above materials were kneaded by the following method to obtain a rubber composition. A closed mixer (content 0.3L) equipped with a temperature control device was used as the first stage of kneading to mix the raw rubber components (samples B1 to B6, B8 to B19, B23 to B26, B27), fillers (silicon oxide 1, silicon oxide 2, carbon black), silane coupling agents, SRAE oil, zinc white and stearic acid at a filling rate of 65% and a rotor speed of 30 rpm to 50 rpm. At this time, the temperature of the closed mixer was controlled to obtain each rubber composition (mixed product) at a discharge temperature of 155°C to 160°C.
[0568] Next, as the second stage of mixing, after the above-obtained mixture is cooled to room temperature, an anti-aging agent is added, and mixing is performed again to improve the dispersion of silicon oxide. In this case, the discharge temperature of the mixture is also adjusted to 155°C to 160°C by temperature control of the mixer. After cooling, as the third stage of mixing, sulfur and vulcanization accelerators 1 and 2 are added to an open mill set at 70°C for mixing to obtain a rubber composition (conjugated diene polymer composition or hydrogenated conjugated diene polymer composition). Afterwards, the obtained rubber composition is molded and vulcanized at 160°C for 20 minutes using a vulcanization press. The rubber composition before vulcanization and the rubber composition after vulcanization are evaluated. Specifically, the following method is used for evaluation.
[0569] The results of Application Comparative Examples 1 to 4, Application Comparative Examples 6 to 9, Application Examples 1 to 2, Application Examples 4 to 11, Application Examples 15 to 17, and Application Example 33 are shown in Tables 2-1 to 2-5.
[0570] Table 3 shows the results of applying Comparative Example 5.
[0571] (Mooney viscosity of the compound)
[0572] The mixture obtained after the second stage kneading and before the third stage kneading was used as a sample, and the viscosity was measured using a Mooney viscometer in accordance with ISO 289 after preheating at 130° C. for 1 minute and rotating the rotor at 2 rpm for 4 minutes.
[0573] Regarding Application Comparative Examples 2 to 4 and Application Examples 1 to 2, 4 to 5, the result of Application Comparative Example 1 was indexed as 100. Regarding Application Examples 6 to 8, the result of Application Comparative Example 6 was indexed as 100. Regarding Application Examples 9 to 11, the result of Application Comparative Example 7 was indexed as 100. The result of Application Comparative Example 8 was indexed as 100. Regarding Application Examples 15 to 17, the result of Application Comparative Example 9 was indexed as 100. Regarding the result of Application Example 33, the result of Application Comparative Example 1 was indexed as 100. Regarding the result of Application Comparative Example 5, the result of Application Comparative Example 10 under the mixing condition D described later was indexed as 100. The smaller the index, the better the processability.
[0574] If the index is 79 or less, it is very good (◎◎ in the table), if the index is 80 to 89, it is good (◎ in the table), if the index is 90 to 99, there is no problem in practical use (○ in the table), if the index is 100 to 105, it is slightly poor (△ in the table), and if the index is 105 or more, there is a problem in practical use (× in the table).
[0575] (Breaking strength and elongation at break, and destructive properties)
[0576] The breaking strength and breaking elongation were measured according to the tensile test method of JIS K6251. The product of the breaking strength and breaking elongation was taken as the destructive property.
[0577] Regarding Application Comparative Examples 2 to 4 and Application Examples 1 to 2, 4 to 5, the result of Application Comparative Example 1 was indexed as 100. Regarding Application Examples 6 to 8, the result of Application Comparative Example 6 was indexed as 100. Regarding Application Examples 9 to 11, the result of Application Comparative Example 7 was indexed as 100. The result of Application Comparative Example 8 was indexed as 100. Regarding Application Examples 15 to 17, the result of Application Comparative Example 9 was indexed as 100. Regarding the result of Application Example 33, the result of Application Comparative Example 1 was indexed as 100. Regarding the result of Application Comparative Example 5, the result of Application Comparative Example 10 under the mixing condition D described later was indexed as 100. The larger the index, the better the breaking strength and breaking elongation (breaking strength), and the breaking characteristics.
[0578] If the index is 121 or more, it is very good (◎◎ in the table), if the index is 111 to 120, it is good (◎ in the table), if the index is 101 to 110, there is no problem in practical use (○ in the table), if the index is 95 to 100, it is slightly poor (△ in the table), and if the index is 94 or less, there is a problem in practical use (× in the table).
[0579] (Fuel saving performance)
[0580] Viscoelastic parameters were measured in torsion mode using a viscoelasticity tester "ARES" manufactured by Rheometric Scientific.
[0581] Tan δ measured at 50° C., a frequency of 10 Hz, and a strain of 3% was used as an index of fuel efficiency.
[0582] Regarding application comparative examples 2 to 4 and application examples 1 to 2, 4 to 5, the result of application comparative example 1 was set to 100 for indexation. Regarding application examples 6 to 8, the result of application comparative example 6 was set to 100 for indexation. Regarding application examples 9 to 11, the result of application comparative example 7 was set to 100 for indexation. The result of application comparative example 8 was set to 100 for indexation. Regarding application examples 15 to 17, the result of application comparative example 9 was set to 100 for indexation. Regarding the result of application example 33, the result of application comparative example 1 was set to 100 for indexation.
[0583] If the index is 121 or more, it is very good (◎◎ in the table), if the index is 111 to 120, it is good (◎ in the table), if the index is 101 to 110, there is no problem in practical use (○ in the table), if the index is 95 to 100, it is slightly poor (△ in the table), if the index is 94 or less, the fuel consumption is worse than the standard product, and the grade in the labeling system may be lowered (× in the table). The results are shown in Tables 2-1 to 2-5 and Table 3.
[0584] [Application Comparative Example 10]
[0585] Sample B8 shown in Table 1-1 was used as a raw rubber component, and a rubber composition containing the raw rubber component was obtained under the following compounding conditions D.
[0586] (Rubber component)
[0587] Conjugated diene polymer or hydrogenated conjugated diene polymer (sample B8): 100 parts by mass
[0588] (Mixing Condition D)
[0589] The amount of each compounding agent added is expressed in parts by mass relative to 100 parts by mass of the rubber component excluding the rubber softener.
[0590] Silicon oxide 1 (trade name "Ultrasil 700 0GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m2 / g): 50.0 parts by mass
[0591] Silicon oxide 2 (trade name "Zeosil Premium 2 00MP" manufactured by Rhodia, nitrogen adsorption specific surface area 220 m2 / g): 25.0 parts by mass
[0592] Carbon black (trade name "SEAST KH (N339)" manufactured by Tokai Tanso Co., Ltd.): 5.0 parts by mass
[0593] Silane coupling agent (trade name "Si75" manufactured by Evonik Degussa, bis(triethoxysilylpropyl) disulfide): 6.0 parts by mass
[0594] SRAE oil (trade name "Process NC140" manufactured by JX Nippon Oil & Energy Corporation): 15.0 parts by mass
[0595] Zinc white: 2.5 parts by mass
[0596] Stearic acid: 1.0 parts by mass
[0597] Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine): 2.0 parts by mass
[0598] Sulfur: 2.2 parts by mass
[0599] Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazolylsulfenamide): 1.7 parts by mass
[0600] Vulcanization accelerator 2 (diphenylguanidine): 2.0 parts by mass
[0601] Total: 212.4 parts by mass
[0602] (Mixing method)
[0603] The above materials were kneaded by the following method to obtain a rubber composition. A closed mixer (content 0.3L) equipped with a temperature control device was used as the first stage of kneading to knead the raw rubber component (sample B8), filler (silicon oxide 1, silicon oxide 2, carbon black), silane coupling agent, SRAE oil, zinc white and stearic acid under the conditions of a filling rate of 65% and a rotor speed of 30rpm to 50rpm. At this time, the temperature of the closed mixer was controlled to obtain each rubber composition (mixed product) under the condition of a discharge temperature of 155°C to 160°C.
[0604] Next, as the second stage of mixing, the above-obtained mixture is cooled to room temperature, an anti-aging agent is added, and mixing is performed again to improve the dispersion of silicon oxide. In this case, the discharge temperature of the mixture is also adjusted to 155°C to 160°C by temperature control of the mixer. After cooling, as the third stage of mixing, sulfur and vulcanization accelerators 1 and 2 are added to an open mill set at 70°C for mixing to obtain a rubber composition. Afterwards, the obtained rubber composition is molded and vulcanized at 160°C for 20 minutes using a vulcanization press. The rubber composition before vulcanization and the rubber composition after vulcanization are evaluated. Specifically, the following method is used for evaluation. The results are shown in Table 3.
[0605] (Mooney viscosity of the compound)
[0606] The mixture obtained after the second stage kneading and before the third stage kneading was used as a sample, and the viscosity was measured using a Mooney viscometer in accordance with ISO 289 after preheating at 130° C. for 1 minute and rotating the rotor at 2 rpm for 4 minutes.
[0607] The result of Comparative Application Example 10 under compounding condition D was indexed by setting it to 100. The smaller the index, the better the processability.
[0608] If the index is 79 or less, it is very good (◎◎ in the table), if the index is 80 to 89, it is good (◎ in the table), if the index is 90 to 99, there is no problem in practical use (○ in the table), if the index is 100 to 105, it is slightly poor (△ in the table), and if the index is 105 or more, there is a problem in practical use (× in the table).
[0609] (Breaking strength and elongation at break, destructive characteristics)
[0610] The breaking strength and breaking elongation were measured according to the tensile test method of JIS K6251. The product of the breaking strength and breaking elongation was taken as the destructive property.
[0611] The result of Comparative Application Example 10 under compounding condition D was indexed by setting it to 100. A larger index indicates better breaking strength and breaking elongation (breaking strength) and breaking characteristics.
[0612] If the index is 121 or more, it is very good (◎◎ in the table), if the index is 111 to 120, it is good (◎ in the table), if the index is 101 to 110, there is no problem in practical use (○ in the table), if the index is 95 to 100, it is slightly poor (△ in the table), and if the index is 94 or less, there is a problem in practical use (× in the table).
[0613]
[0614] [Table 2-2]
[0615]
[0616] [Table 2-3]
[0617]
[0618] [Table 2-4]
[0619]
[0620] [Table 2-5]
[0621]
[0622] [Table 3]
[0623]
[0624] [Production of Hydrogenated Conjugated Diene Polymer Composition (Oil-Extended Polymer)]
[0625] (Comparative Example 10) Hydrogenated conjugated diene polymer composition (Sample C1)
[0626] Two tank-type pressure vessels equipped with a stirrer and a jacket for temperature control were connected as a polymerization reactor. The tank-type pressure vessel was a tank-type reactor with a stirrer having an internal volume of 10 L, a ratio (L / D) of the internal height (L) to the diameter (D) of 4.0, an inlet at the bottom, and an outlet at the top.
[0627] 1,3-butadiene (initial butadiene) from which water had been removed in advance was mixed at 17.7 g / min, styrene at 10.9 g / min, and n-hexane at 175.2 g / min. A static mixer was set in the middle of the pipe supplying the mixed solution to the inlet of the reactor, and n-butyl lithium (treated n-butyl lithium) for residual impurity inert treatment was added to the static mixer at 0.105 mmol / min, mixed, and continuously supplied to the bottom of the reactor. Furthermore, 2,2-bis(2-tetrahydrofuryl) propane (BOP) as a polar substance was supplied at a rate of 0.034 mmol / min, and n-butyl lithium (polymerization initiation n-butyl lithium) as a polymerization initiator was supplied at a rate of 0.122 mmol / min to the bottom of the first reactor that was vigorously mixed with a stirrer, and polymerization was initiated, and the temperature inside the reactor was maintained at 67°C.
[0628] The polymer solution was continuously withdrawn from the top of the first reactor and continuously supplied to the bottom of the second reactor to continue the reaction at 70° C., and was further supplied to a static mixer from the top of the second reactor.
[0629] Next, N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was continuously added to the polymer solution flowing out of the outlet of the reactor at a rate of 0.041 mmol / min, and mixed using a static mixer to perform a coupling reaction. At this time, the time until the coupling agent was added to the polymer solution flowing out of the outlet of the reactor was 4.8 minutes, the temperature was 68°C, and the difference between the temperature in the polymerization step and the temperature until the coupling agent was added was 2°C.
[0630] Next, methanol as a reaction terminator was added to the polymer solution subjected to the coupling reaction at a rate of 0.019 mmol / min.
[0631] The obtained conjugated diene polymer solution was transferred to another reactor, and 60 ppm of the above-prepared hydrogenation catalyst (T) was added based on Ti relative to 100 parts by mass of the conjugated diene polymer, and a hydrogenation reaction was carried out for 30 minutes under the conditions of a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. to obtain a solution of a hydrogenated conjugated diene polymer. The hydrogenation rate of the structural unit derived from butadiene in the obtained hydrogenated conjugated diene polymer was 50.0%.
[0632] Next, 0.2 g of an antioxidant (BHT) was continuously added to the obtained solution of the hydrogenated conjugated diene polymer relative to 100 g of the polymer. SRAE oil (JOMO Process NC140 manufactured by JX Nippon Mining and Petrochemical Corporation) as a rubber softener was continuously added in an amount of 25.0 g relative to 100 g of the polymer at the same time as the antioxidant, and mixed using a static mixer. The solvent was removed by stripping to obtain a hydrogenated conjugated diene polymer composition (sample C1).
[0633] The physical properties of sample C1 are shown in Table 4-1.
[0634] From the measurement results, it is found that the structure of the conjugated diene polymer in Sample C1 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0635] (Comparative Example 11) Conjugated diene polymer composition (Sample C2)
[0636] Two tank-type pressure vessels equipped with a stirrer and a jacket for temperature control were connected as a polymerization reactor. The tank-type pressure vessel was a tank-type reactor with a stirrer having an internal volume of 10 L, a ratio (L / D) of the internal height (L) to the diameter (D) of 4.0, an inlet at the bottom, and an outlet at the top.
[0637] 1,3-butadiene (initial butadiene) from which water had been removed in advance was mixed at 14.2 g / min, styrene at 10.9 g / min, and n-hexane at 175.2 g / min. A static mixer was set in the middle of the pipe supplying the mixed solution to the inlet of the reactor, and n-butyl lithium (treated n-butyl lithium) for inert treatment of residual impurities was added to the static mixer at 0.105 mmol / min, mixed, and continuously supplied to the bottom of the reactor. Furthermore, 2,2-bis(2-tetrahydrofuryl) propane (BOP) as a polar substance was supplied at a rate of 0.056 mmol / min, and n-butyl lithium (polymerization initiation n-butyl lithium) as a polymerization initiator was supplied at a rate of 0.215 mmol / min to the bottom of the first reactor that was vigorously mixed with a stirrer, and polymerization was initiated, and the temperature inside the reactor was maintained at 67°C.
[0638] The polymer solution was continuously withdrawn from the top of the first reactor and continuously supplied to the bottom of the second reactor, and the reaction was continued at 70°C, and further supplied to the static mixer from the top of the second reactor. After the polymerization was sufficiently stable, trimethoxy(4-vinylphenyl)silane (BS-1) as a branching agent was added from the bottom of the second reactor at a rate of 0.032 mmol / min while copolymerizing 1,3-butadiene and styrene, and polymerization and branching reactions were performed to obtain a conjugated diene polymer having a main chain branch structure.
[0639] Next, 1,3-butadiene from which water had been removed in advance (additional butadiene) was additionally added from the middle portion of the second reactor at a rate of 3.5 g / min to further carry out the polymerization reaction.
[0640] Next, N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5) as a coupling agent was continuously added to the polymer solution flowing out of the outlet of the reactor at a rate of 0.013 mmol / min, and mixed using a static mixer to perform a coupling reaction. At this time, the time until the coupling agent was added to the polymer solution flowing out of the outlet of the reactor was 4.8 minutes, the temperature was 68°C, and the difference between the temperature in the polymerization step and the temperature until the coupling agent was added was 2°C.
[0641] Next, methanol as a reaction terminator was added to the polymer solution after the coupling reaction at a rate of 0.018 mmol / min, and then 0.2 g of an antioxidant (BHT) was continuously added relative to 100 g of the polymer at 0.055 g / min (n-hexane solution). SRAE oil (JOMO Process NC140 manufactured by JX Nippon Mining and Petrochemical Corporation) as a rubber softener was continuously added at 25.0 g relative to 100 g of the polymer at the same time as the antioxidant, and mixed using a static mixer. The solvent was removed by stripping to obtain a conjugated diene polymer composition (sample C2).
[0642] The physical properties of sample C2 are shown in Table 4-1.
[0643] It should be noted that, regarding the polymer before the addition of the branching agent, the polymer after the addition of the branching agent, and the polymer in each process after the addition of the coupling agent, the structure of the conjugated diene polymer is identified by comparing the molecular weight determined based on GPC with the degree of branching determined based on GPC with a viscometer. The structure of each sample is identified in the same manner below. From the results of the measurement, it can be seen that the structure of the conjugated diene polymer after the addition of the branching agent in sample C2 has a star-shaped polymer structure with an average of 4.2 branches, and the conjugated diene polymer after the addition of the coupling agent has a portion of a vinyl monomer containing an alkoxysilyl group in an average of 4 branches of the star-shaped structure.
[0644] (Comparative Example 12) Hydrogenated conjugated diene polymer composition (Sample C3)
[0645] Two tank-type pressure vessels equipped with a stirrer and a jacket for temperature control were connected as a polymerization reactor. The tank-type pressure vessel was a tank-type reactor with a stirrer having an internal volume of 10 L, a ratio (L / D) of the internal height (L) to the diameter (D) of 4.0, an inlet at the bottom, and an outlet at the top.
[0646] 1,3-butadiene (initial butadiene) from which water had been removed in advance was mixed at 14.2 g / min, styrene at 10.9 g / min, and n-hexane at 175.2 g / min. A static mixer was set in the middle of the pipe supplying the mixed solution to the inlet of the reactor, and n-butyl lithium (treated n-butyl lithium) for inert treatment of residual impurities was added to the static mixer at 0.105 mmol / min, mixed, and continuously supplied to the bottom of the reactor. Furthermore, 2,2-bis(2-tetrahydrofuryl) propane (BOP) as a polar substance was supplied at a rate of 0.056 mmol / min, and n-butyl lithium (polymerization initiation n-butyl lithium) as a polymerization initiator was supplied at a rate of 0.215 mmol / min to the bottom of the first reactor that was vigorously mixed with a stirrer, and polymerization was initiated, and the temperature inside the reactor was maintained at 67°C.
[0647] The polymer solution was continuously withdrawn from the top of the first reactor and continuously supplied to the bottom of the second reactor, and the reaction was continued at 70°C, and further supplied to the static mixer from the top of the second reactor. After the polymerization was sufficiently stable, trimethoxy(4-vinylphenyl)silane (BS-1) as a branching agent was added from the bottom of the second reactor at a rate of 0.032 mmol / min while copolymerizing 1,3-butadiene and styrene, and polymerization and branching reactions were performed to obtain a conjugated diene polymer having a main chain branch structure.
[0648] Next, 1,3-butadiene from which water had been removed in advance (additional butadiene) was additionally added from the middle portion of the second reactor at a rate of 3.5 g / min to further carry out the polymerization reaction.
[0649] Next, N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5) as a coupling agent was continuously added to the polymer solution flowing out of the outlet of the reactor at a rate of 0.013 mmol / min, and mixed using a static mixer to perform a coupling reaction. At this time, the time until the coupling agent was added to the polymer solution flowing out of the outlet of the reactor was 4.8 minutes, the temperature was 68°C, and the difference between the temperature in the polymerization step and the temperature until the coupling agent was added was 2°C.
[0650] Next, methanol as a reaction terminator was added to the polymer solution subjected to the coupling reaction at a rate of 0.018 mmol / min to obtain a solution of a conjugated diene polymer.
[0651] The obtained conjugated diene polymer solution was transferred to another reactor, and 60 ppm of the above-prepared hydrogenation catalyst (T) was added based on Ti relative to 100 parts by mass of the conjugated diene polymer, and a hydrogenation reaction was carried out for 20 minutes under the conditions of a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. to obtain a hydrogenated conjugated diene polymer solution. The hydrogenation rate of the structural unit derived from butadiene in the obtained hydrogenated conjugated diene polymer was 20.0%.
[0652] Next, 0.2 g of an antioxidant (BHT) was continuously added to the obtained solution of the hydrogenated conjugated diene polymer relative to 100 g of the polymer. SRAE oil (JOMO Process NC140 manufactured by JX Nippon Mining and Petrochemical Corporation) as a rubber softener was continuously added in an amount of 25.0 g relative to 100 g of the polymer at the same time as the antioxidant, and mixed using a static mixer. The solvent was removed by stripping to obtain a hydrogenated conjugated diene polymer composition (sample C3).
[0653] The physical properties of sample C3 are shown in Table 4-1.
[0654] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in sample C3 has a star-shaped polymer structure with an average of 4.2 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 4 branches of the star structure.
[0655] (Examples 18 to 20) Hydrogenated conjugated diene polymer compositions (samples C4, C5, and C6, respectively)
[0656] Hydrogenated conjugated diene polymer compositions (Sample C4, Sample C5, and Sample C6) were obtained by the same operation as in Comparative Example 12 except that the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rates of the hydrogenated conjugated diene polymers of Sample C4, Sample C5, and Sample C6 were 55.0%, 87.0%, and 93.0%, respectively.
[0657] Sample C4, Sample C5, and Sample C6 were analyzed, and the results are shown in Table 4-1.
[0658] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in samples C4, C5 and C6 has a star-shaped polymer structure with an average of 4.2 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 4 branches of the star structure.
[0659] (Examples 21 to 23) Hydrogenated conjugated diene polymer compositions (samples C7, C8, and C9, respectively)
[0660] Hydrogenated conjugated diene polymer compositions (Sample C7, Sample C8, Sample C9) were obtained by the same operation as Comparative Example 12 except that the accumulated flow rate of hydrogen in the hydrogenation reaction was adjusted, except that the amount of 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.056 mmol / min, the amount of n-butyl lithium (polymerization initiator n-butyl lithium) as a polymerization initiator was changed to 0.163 mmol / min, the amount of trimethoxy(4-vinylphenyl)silane (BS-1) as a branching agent was changed to 0.033 mmol / min, the amount of 3-(4-methylpiperazin-1-yl)propyltriethoxysilane (Compound 6) as a coupling agent was changed to 0.011 mmol / min, and the amount of methanol as a reaction terminator was changed to 0.016 mmol / min. The hydrogenated conjugated diene polymer compositions of Sample C7, Sample C8, and Sample C9 had hydrogenation rates of 50.0%, 84.0%, and 93.0%, respectively.
[0661] Sample C7, Sample C8, and Sample C9 were analyzed, and the results are shown in Table 4-1.
[0662] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in samples C7, C8 and C9 has a star-shaped polymer structure with an average of 4.2 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 1 branch of the star structure.
[0663] (Comparative Example 13) Hydrogenated conjugated diene polymer composition (Sample C10)
[0664] A hydrogenated conjugated diene polymer composition (Sample C10) was obtained by the same operation as Comparative Example 10 except that the initial butadiene was changed to 21.5 g / min, the styrene was changed to 7.2 g / min, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.036 mmol / min, the n-butyl lithium (polymerization initiator n-butyl lithium) as a polymerization initiator was changed to 0.130 mmol / min, the N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was changed to 0.044 mmol / min, and the methanol as a reaction terminator was changed to 0.02 mmol / min, and the accumulated flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rate in the hydrogenated conjugated diene polymer of Sample C10 was 50.0%.
[0665] Sample C10 was analyzed and the results are shown in Table 4-2.
[0666] From the measurement results, it is understood that the structure of the conjugated diene polymer in sample C10 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0667] (Examples 24 to 26) Hydrogenated conjugated diene polymer compositions (samples C11, C12, and C13, respectively)
[0668] The initial butadiene was changed to 17.2 g / min, styrene was changed to 7.2 g / min, 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.051 mmol / min, n-butyl lithium as a polymerization initiator (polymerization initiator n-butyl lithium) was changed to 0.170 mmol / min, the branching agent was changed to dimethoxymethyl(4-vinylphenyl)silane (BS-2) 0.041 mmol / min, and the additional butadiene was changed to 4.3 g / min, the coupling agent was changed to 3,3'-(piperazine-1,4-diyl)bis(N,N-bis(3-(triethoxysilyl)propyl)propane-1-amine)(Compound 7) 0.012mmol / min, the methanol as the reaction terminator was changed to 0.016mmol / min, and the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. A hydrogenated conjugated diene polymer composition (Sample C11, Sample C12, Sample C13) was obtained by the same operation as Comparative Example 12. The hydrogenation rates in the hydrogenated conjugated diene polymers of Sample C11, Sample C12, and Sample C13 were 50.0%, 82.0%, and 95.0%, respectively.
[0669] Sample C11, Sample C12, and Sample C13 were analyzed, and the results are shown in Table 4-2.
[0670] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in samples C11, C12 and C13 has an average of 3 branches in a star-shaped polymer structure, and the conjugated diene polymer after adding the coupling agent has an average of 3.8 branches of the star-shaped structure derived from a vinyl monomer containing an alkoxysilyl group.
[0671] (Comparative Example 14) Hydrogenated conjugated diene polymer composition (Sample C14)
[0672] A hydrogenated conjugated diene polymer composition (Sample C14) was obtained by the same operation as Comparative Example 10 except that the initial butadiene was changed to 17.2 g / min, the styrene was changed to 11.5 g / min, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.054 mmol / min, the n-butyl lithium (polymerization initiator n-butyl lithium) as a polymerization initiator was changed to 0.120 mmol / min, the N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane (Compound 1) as a coupling agent was changed to 0.041 mmol / min, and the methanol as a reaction terminator was changed to 0.018 mmol / min, and the accumulated flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rate in the hydrogenated conjugated diene polymer of Sample C14 was 60%.
[0673] Sample C14 was analyzed and the results are shown in Table 4-3.
[0674] From the measurement results, it is found that the structure of the conjugated diene polymer in sample C14 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0675] (Examples 27 to 29) Hydrogenated conjugated diene polymer compositions (samples C15, C16, and C17, respectively)
[0676] Hydrogenated conjugated diene polymer compositions (samples C15, C16, and C17) were obtained by the same operation as in Comparative Example 10, except that the initial butadiene was changed to 17.2 g / min, the styrene was changed to 11.5 g / min, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.067 mmol / min, the n-butyllithium (polymerization initiator n-butyllithium) as a polymerization initiator was changed to 0.159 mmol / min, the coupling agent was changed to 0.017 mmol / min of N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5), and the methanol as a reaction terminator was changed to 0.024 mmol / min, and the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rates in the hydrogenated conjugated diene polymers of Sample C15, Sample C16, and Sample C17 were 60.0%, 82.0%, and 93.0%, respectively.
[0677] Sample C15, Sample C16, and Sample C17 were analyzed, and the results are shown in Table 4-3.
[0678] The measurement results show that the structure of the conjugated diene polymer before the addition of the coupling agent in samples C15, C16, and C17 has a linear polymer structure and does not have a star-shaped polymer.
[0679] (Comparative Example 15) Hydrogenated conjugated diene polymer composition (Sample C18)
[0680] A conjugated diene polymer composition (sample C18) was obtained by the same operation as in Comparative Example 10, except that the initial butadiene was changed to 17.9 g / min, styrene was changed to 9.8 g / min, cyclohexane was changed to 145.3 g / min, 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.098 mmol / min, n-butyllithium (polymerization initiator n-butyllithium) as a polymerization initiator was changed to 0.242 mmol / min, the coupling agent was changed to N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5) 0.030 mmol / min, and methanol as a reaction terminator was changed to 0.044 mmol / min. No hydrogenation catalyst (T) was added and no hydrogenation reaction was carried out.
[0681] Sample C18 was analyzed and the results are shown in Table 4-4.
[0682] From the measurement results, it is found that the structure of the conjugated diene polymer in sample C18 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0683] (Example 30) Hydrogenated conjugated diene polymer composition (Sample C19)
[0684] A hydrogenated conjugated diene polymer composition (Sample C19) was obtained by the same operation as in Comparative Example 10 except that the initial butadiene was changed to 17.9 g / min, styrene was changed to 9.8 g / min, cyclohexane was changed to 145.3 g / min, 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.098 mmol / min, n-butyl lithium (polymerization initiator n-butyl lithium) as a polymerization initiator was changed to 0.242 mmol / min, the coupling agent was changed to 0.030 mmol / min of N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5), and methanol as a reaction terminator was changed to 0.044 mmol / min, and the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. The hydrogenation rate in the hydrogenated conjugated diene polymer of Sample C19 was 80%.
[0685] Sample C19 was analyzed and the results are shown in Table 4-4.
[0686] From the measurement results, it is found that the structure of the conjugated diene polymer in sample C19 before the addition of the coupling agent has a linear polymer structure and does not have a star-shaped polymer.
[0687] (Comparative Example 16)
[0688] The same operation as in Comparative Example 10 was carried out except that the initial butadiene was changed to 17.9 g / min, the styrene was changed to 9.8 g / min, the cyclohexane was changed to 145.3 g / min, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as the polar substance was changed to 0.018 mmol / min, the n-butyllithium (polymerization initiator n-butyllithium) as the polymerization initiator was changed to 0.121 mmol / min, the coupling agent was changed to 0.012 mmol / min of N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5), the methanol as the reaction terminator was changed to 0.025 mmol / min, and the hydrogenation catalyst (T) was added in an amount of 100 ppm based on Ti relative to 100 parts by mass of the conjugated diene polymer. Since the viscosity became extremely high during the hydrogenation reaction, the hydrogenation reaction did not proceed, and the reaction was stopped during the hydrogenation reaction to obtain a conjugated diene polymer composition (sample C20).
[0689] Sample C20 was analyzed and the results are shown in Table 4-4.
[0690] From the measurement results, it is found that the structure of the conjugated diene polymer before the addition of the coupling agent in the sample C20 has a linear polymer structure and does not have a star-shaped polymer.
[0691] (Example 32)
[0692] The same operation as in Comparative Example 10 was carried out except that the initial butadiene was changed to 17.9 g / min, the styrene was changed to 9.8 g / min, the cyclohexane was 145.3 g / min, the 2,2-bis(2-tetrahydrofuryl)propane (BOP) as the polar substance was changed to 0.018 mmol / min, the n-butyllithium (polymerization initiator n-butyllithium) as the polymerization initiator was changed to 0.121 mmol / min, the coupling agent was changed to 0.012 mmol / min of N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine (Compound 5), the methanol as the reaction terminator was changed to 0.025 mmol / min, 200 ppm of the hydrogenation catalyst (T) was added based on Ti relative to 100 parts by mass of the conjugated diene polymer, and cyclohexane was further added so that the copolymer concentration in cyclohexane became 12% by mass. Since the viscosity became extremely high during the hydrogenation reaction, the hydrogenation reaction did not proceed, and the reaction was stopped during the hydrogenation reaction to obtain a conjugated diene polymer composition (sample C21).
[0693] Sample C21 was analyzed and the results are shown in Table 4-4.
[0694] From the measurement results, it is found that the structure of the conjugated diene polymer before the addition of the coupling agent in the sample C21 has a linear polymer structure and does not have a star-shaped polymer.
[0695] (Example 33)
[0696] The initial butadiene was changed to 14.3 g / min, styrene was changed to 9.8 g / min, 2,2-bis(2-tetrahydrofuryl)propane (BOP) as a polar substance was changed to 0.027 mmol / min, n-butyl lithium as a polymerization initiator (polymerization initiator n-butyl lithium) was changed to 0.194 mmol / min, trimethoxy(4-vinylphenyl)silane (BS-1) as a branching agent was changed to 0.048 mmol / min, and the additional butadiene was changed to The hydrogenation reaction was carried out without any problem by the same operation as in Comparative Example 12, except that the coupling agent was changed to 0.010 mmol / min of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (Compound 2), the methanol as the reaction terminator was changed to 0.010 mmol / min, and the cumulative flow rate of hydrogen in the hydrogenation reaction was adjusted. A hydrogenated conjugated diene polymer composition (Sample C22) was obtained. The hydrogenation rate in the hydrogenated conjugated diene polymer of Sample C22 was 50%.
[0697] Sample C22 was analyzed and the results are shown in Table 4-4.
[0698] The measurement results show that the structure of the conjugated diene polymer after adding the branching agent in sample C22 has a star-shaped polymer structure with an average of 3.9 branches, and the conjugated diene polymer after adding the coupling agent has a portion derived from a vinyl monomer containing an alkoxysilyl group in an average of 3.6 branches of the star structure.
[0699]
[0700] [Table 4-2]
[0701]
[0702] [Table 4-3]
[0703]
[0704] [Table 4-4]
[0705]
[0706] The branching agents and coupling agents described in Tables 4-1 to 4-4 are the following compounds.
[0707] [Branching agent]
[0708] BS-1: Trimethoxy(4-vinylphenyl)silane
[0709] BS-2: Dimethoxymethyl (4-vinylphenyl) silane
[0710] [Coupling agent]
[0711] Compound 1: N,N-bis(trimethylsilyl)aminopropylmethyltriethoxysilane Compound 5: N,N,N',N'-tetrakis(3-trimethoxysilylpropyl)-1,3-propylenediamine Compound 6: 3-(4-methylpiperazin-1-yl)propyltriethoxysilane
[0712] Compound 7: 3,3'-(piperazine-1,4-diyl)bis(N,N-bis(3-(triethoxysilyl)propyl)propane-1-amine)
[0713] [Application Examples 19 to 31 and Application Comparative Examples 11 to 16, Application Comparative Example 19, Application Examples 34 and 35]
[0714] Samples C1 to C19 and C20 to C22 shown in Tables 4-1 to 4-4 were used as raw rubber components, and rubber compositions containing the raw rubber components were obtained according to the blending condition E shown below.
[0715] (Rubber component)
[0716] Conjugated diene polymer composition or hydrogenated conjugated diene polymer composition (samples C1 to C19, C20 to C22): 100 parts by mass (excluding parts by mass of rubber softener)
[0717] (Mixing Condition E)
[0718] The amount of each compounding agent added is expressed in parts by mass relative to 100 parts by mass of the rubber component excluding the rubber softener.
[0719] Silicon oxide 1 (trade name "Ultrasil 700 0GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m 2 / g): 50.0 parts by mass
[0720] Silicon oxide 2 (trade name "Zeosil Premium 2 00MP" manufactured by Rhodia, nitrogen adsorption specific surface area 220m 2 / g): 25.0 parts by mass
[0721] Carbon black (trade name "SEAST KH (N339)" manufactured by Tokai Tanso Co., Ltd.): 5.0 parts by mass
[0722] Silane coupling agent (trade name "Si75" manufactured by Evonik Degussa, bis(triethoxysilylpropyl) disulfide): 6.0 parts by mass
[0723] SRAE oil (trade name "Process NC140" manufactured by JX Nippon Mining & Energy Corporation): 37.5 parts by mass (including the amount added in advance as a rubber softener contained in samples C1 to C19)
[0724] Zinc white: 2.5 parts by mass
[0725] Stearic acid: 1.0 parts by mass
[0726] Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine): 2.0 parts by mass
[0727] Sulfur: 2.2 parts by mass
[0728] Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazolylsulfenamide): 1.7 parts by mass
[0729] Vulcanization accelerator 2 (diphenylguanidine): 2.0 parts by mass
[0730] Total: 234.9 parts by mass
[0731] (Mixing method)
[0732] The above materials were kneaded by the following method to obtain a rubber composition. A closed mixer (content 0.3L) equipped with a temperature control device was used as the first stage of kneading to knead the raw rubber components (samples C1 to C19, C20 to C22), fillers (silicon oxide 1, silicon oxide 2, carbon black), silane coupling agents, SRAE oil, zinc white and stearic acid at a filling rate of 65% and a rotor speed of 30 rpm to 50 rpm. At this time, the temperature of the closed mixer was controlled to obtain each rubber composition (mixed product) at a discharge temperature of 155°C to 160°C.
[0733] Next, as the second stage of mixing, the above-obtained mixture is cooled to room temperature, an anti-aging agent is added, and mixing is performed again to improve the dispersion of silicon oxide. In this case, the discharge temperature of the mixture is also adjusted to 155°C to 160°C by temperature control of the mixer. After cooling, as the third stage of mixing, sulfur and vulcanization accelerators 1 and 2 are added to an open mill set at 70°C for mixing to obtain a rubber composition. Thereafter, the obtained rubber composition is molded and vulcanized at 160°C for 20 minutes using a vulcanization press. The rubber composition before vulcanization and the rubber composition after vulcanization are evaluated. Specifically, the evaluation is performed by the following method.
[0734] Regarding Application Comparative Examples 11 to 15, Application Examples 19 to 30, Application Comparative Example 19, and Application Examples 34 and 35, the results are shown in Tables 5-1 to 5-3.
[0735] Table 6 shows the results of Application Comparative Example 16 and Application Example 31.
[0736] (Mooney viscosity of the compound)
[0737] The mixture obtained after the second stage kneading and before the third stage kneading was used as a sample, and the viscosity was measured using a Mooney viscometer in accordance with ISO 289 after preheating at 130° C. for 1 minute and rotating the rotor at 2 rpm for 4 minutes.
[0738] Regarding Application Comparative Examples 12 and 13 and Application Examples 19 to 24, the result of Comparative Example 11 was indexed as 100. Regarding Application Examples 25 to 27, the result of Comparative Example 14 was indexed as 100. Regarding Application Examples 28 to 30, the result of Comparative Example 15 was indexed as 100. Regarding Application Examples 34 and 35, the result of Comparative Example 19 was indexed as 100. Regarding the results of Application Example 31 and Application Comparative Example 16 under the compounding condition E, the result of Application Comparative Example 17 under the compounding condition F described later was indexed as 100. The smaller the index, the better the processability.
[0739] If the index is 79 or less, it is very good (◎◎ in the table), if the index is 80 to 89, it is good (◎ in the table), if the index is 90 to 99, there is no problem in practical use (○ in the table), if the index is 100 to 105, it is slightly poor (△ in the table), and if the index is 105 or more, there is a problem in practical use (× in the table).
[0740] (Breaking strength and elongation at break, destructive characteristics)
[0741] The breaking strength and breaking elongation were measured according to the tensile test method of JIS K6251. The product of the breaking strength and breaking elongation was taken as the destructive property.
[0742] Regarding Application Comparative Examples 12 and 13 and Application Examples 19 to 24, the result of Application Comparative Example 11 was indexed as 100. Regarding Application Examples 25 to 27, the result of Application Comparative Example 14 was indexed as 100. Regarding Application Examples 28 to 30, the result of Application Comparative Example 15 was indexed as 100. Regarding Application Examples 34 and 35, the result of Application Comparative Example 19 was indexed as 100. Regarding the results of Application Example 31 and Application Comparative Example 16 under the compounding condition E, the result of Application Comparative Example 17 under the compounding condition F described later was indexed as 100. The larger the index, the better the breaking strength and breaking elongation, as well as the destructive characteristics.
[0743] If the index is 121 or more, it is very good (◎◎ in the table), if the index is 111 to 120, it is good (◎ in the table), if the index is 101 to 110, there is no problem in practical use (○ in the table), if the index is 95 to 100, it is slightly poor (△ in the table), and if the index is 94 or less, there is a problem in practical use (× in the table).
[0744] (Fuel saving performance)
[0745] Viscoelastic parameters were measured in torsion mode using a viscoelasticity tester "ARES" manufactured by Rheometric Scientific.
[0746] Tan δ measured at 50° C., a frequency of 10 Hz, and a strain of 3% was used as an index of fuel efficiency.
[0747] Regarding Application Comparative Examples 12 and 13 and Application Examples 19 to 24, the result of Application Comparative Example 11 was indexed as 100. Regarding Application Examples 25 to 27, the result of Application Comparative Example 14 was indexed as 100. Regarding Application Examples 28 to 30, the result of Application Comparative Example 15 was indexed as 100. Regarding Application Examples 34 and 35, the result of Application Comparative Example 19 was indexed as 100. Regarding the results of Application Example 31 and Application Comparative Example 16 under the blending condition E, the result of Application Comparative Example 17 under the blending condition F described later was indexed as 100.
[0748] If the index is 121 or more, it is very good (◎◎ in the table), if the index is 111 to 120, it is good (◎ in the table), if the index is 101 to 110, there is no problem in practical use (○ in the table), if the index is 95 to 100, it is slightly poor (△ in the table), if the index is 94 or less, the fuel consumption is worse than the standard product, and the grade in the labeling system may be lowered (× in the table). The results are shown in Tables 5-1 to 5-3 and Table 6.
[0749] [Application Example 32 and Application Comparative Example 17]
[0750] Samples C18 and C19 shown in Table 4-3 were used as raw rubber components, and rubber compositions containing the raw rubber components were obtained under the blending conditions F shown below.
[0751] (Rubber component)
[0752] Conjugated diene polymer composition or hydrogenated conjugated diene polymer composition (samples C18 and C19): 100 parts by mass (excluding parts by mass of rubber softener)
[0753] (Mixing Condition F)
[0754] The amount of each compounding agent added is expressed in parts by mass relative to 100 parts by mass of the rubber component excluding the rubber softener.
[0755] Silicon oxide 1 (trade name "Ultrasil 700 0GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m 2 / g): 50.0 parts by mass
[0756] Silicon oxide 2 (trade name "Zeosil Premium 2 00MP" manufactured by Rhodia, nitrogen adsorption specific surface area 220m 2 / g): 25.0 parts by mass
[0757] Carbon black (trade name "SEAST KH (N339)" manufactured by Tokai Tanso Co., Ltd.): 5.0 parts by mass
[0758] Silane coupling agent (trade name "Si75" manufactured by Evonik Degussa, bis(triethoxysilylpropyl) disulfide): 6.0 parts by mass
[0759] SRAE oil (trade name "Process NC140" manufactured by JX Nippon Mining and Petrochemical Corporation): 27.5 parts by mass (including the amount added in advance as a rubber softener contained in samples C18 and C19)
[0760] Zinc white: 2.5 parts by mass
[0761] Stearic acid: 1.0 parts by mass
[0762] Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine): 2.0 parts by mass
[0763] Sulfur: 2.2 parts by mass
[0764] Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazolylsulfenamide): 1.7 parts by mass
[0765] Vulcanization accelerator 2 (diphenylguanidine): 2.0 parts by mass
[0766] Total: 224.9 parts by mass
[0767] (Mixing method)
[0768] The above materials were kneaded by the following method to obtain a rubber composition. A closed mixer (content 0.3L) equipped with a temperature control device was used as the first stage of kneading, and the raw rubber components (samples C18 and C19), fillers (silicon oxide 1, silicon oxide 2, carbon black), silane coupling agents, SRAE oil, zinc white and stearic acid were kneaded under the conditions of a filling rate of 65% and a rotor speed of 30 rpm to 50 rpm. At this time, the temperature of the closed mixer was controlled, and each rubber composition (mixed product) was obtained under the condition of a discharge temperature of 155°C to 160°C.
[0769] Next, as the second stage of mixing, the above-obtained mixture is cooled to room temperature, an anti-aging agent is added, and mixing is performed again to improve the dispersion of silicon oxide. In this case, the discharge temperature of the mixture is also adjusted to 155°C to 160°C by temperature control of the mixer. After cooling, as the third stage of mixing, sulfur and vulcanization accelerators 1 and 2 are added to an open mill set at 70°C for mixing to obtain a rubber composition. Afterwards, the obtained rubber composition is molded and vulcanized at 160°C for 20 minutes using a vulcanizing press. The rubber composition before vulcanization and the rubber composition after vulcanization are evaluated. Specifically, the following method is used for evaluation. The results are shown in Table 6.
[0770] (Mooney viscosity of the compound)
[0771] The mixture obtained after the second stage kneading and before the third stage kneading was used as a sample, and the viscosity was measured using a Mooney viscometer in accordance with ISO 289 after preheating at 130° C. for 1 minute and rotating the rotor at 2 rpm for 4 minutes.
[0772] The result of Example 32 under the compounding condition F was indexed by setting the result of Comparative Example 17 under the compounding condition F as 100. The smaller the index, the better the processability.
[0773] If the index is 79 or less, it is very good (◎◎ in the table), if the index is 80 to 89, it is good (◎ in the table), if the index is 90 to 99, there is no problem in practical use (○ in the table), if the index is 100 to 105, it is slightly poor (△ in the table), and if the index is 105 or more, there is a problem in practical use (× in the table).
[0774] (Breaking strength and elongation at break, destructive characteristics)
[0775] The breaking strength and breaking elongation were measured according to the tensile test method of JIS K6251. The product of the breaking strength and breaking elongation was taken as the destructive property.
[0776] The results of Example 32 under the compounding condition F were indexed by setting the results of Comparative Example 17 under the compounding condition F as 100. The smaller the index, the better the processability. The larger the index, the better the breaking strength and breaking elongation (breaking strength), and the breaking characteristics.
[0777] If the index is 121 or more, it is very good (◎◎ in the table), if the index is 111 to 120, it is good (◎ in the table), if the index is 101 to 110, there is no problem in practical use (○ in the table), if the index is 95 to 100, it is slightly poor (△ in the table), and if the index is 94 or less, there is a problem in practical use (× in the table).
[0778] (Fuel saving performance)
[0779] Viscoelastic parameters were measured in torsion mode using a viscoelasticity tester "ARES" manufactured by Rheometric Scientific.
[0780] Tan δ measured at 50° C., a frequency of 10 Hz, and a strain of 3% was used as an index of fuel efficiency.
[0781] The result of Example 32 under the compounding condition F was indexed by setting the result of Comparative Example 17 under the compounding condition F to 100.
[0782] If the index is 121 or above, it is very good (◎◎ in the table); if the index is 111-120, it is good (◎ in the table); if the index is 101-110, there is no problem in practical use (○ in the table); if the index is 95-100, it is slightly poor (△ in the table); if the index is 94 or below, the fuel consumption is inferior to the benchmark product, and the grade in the labeling system may be lowered (× in the table).
[0783] The results are shown in Tables 5-1 to 5-3 and Table 6.
[0784]
[0785] [Table 5-2]
[0786]
[0787] [Table 5-3]
[0788]
[0789]
[0790] [Application Examples 36 to 54 and Application Comparative Examples 20 to 24]
[0791] According to the raw rubber components and compounding conditions G-1 to G-13 shown in Tables 7-1 and 7-2, rubber compositions containing the raw rubber components were obtained by the same kneading method as in the compounding condition C described above.
[0792] Furthermore, the Mooney viscosity, breaking strength, breaking elongation, fracture characteristics, and fuel efficiency performance of the compound were measured by the same method as the evaluation method of the rubber composition before and after vulcanization.
[0793] The results of Examples 36 to 46 were indexed by setting the result of Comparative Example 20 to 100. The results of Example 47 were indexed by setting the result of Comparative Example 21 to 100. The results of Example 48 were indexed by setting the result of Comparative Example 22 to 100. The results of Examples 49 to 52 were indexed by setting the result of Comparative Example 23 to 100. The results of Examples 53 and 54 were indexed by setting the result of Comparative Example 24 to 100.
[0794] The evaluation results are shown in Table 8-1 and Table 8-2.
[0795]
[0796] Silicon oxide 3: VN3 (N2SA: 175m 2 / g)
[0797] Silicon oxide 4: 115GR (N2SA: 115m 2 / g)
[0798] Silicon oxide 5: 9000GR (N2SA: 235m 2 / g)
[0799] Carbon black 2: Diablack N339 (N2SA: 96m 2 / g, DBP absorption value: 124mL / 100g)
[0800] ·Carbon black 3: Structural material N330 manufactured by Cabot Japan Co., Ltd. (N2SA: 75m 2 / g)
[0801] SRAE oil (trade name "Process NC140" manufactured by JX Nippon Petrochemical Corporation)
[0802] Softener 1: Diana Process AH-24 (aromatic oil) manufactured by Idemitsu Kosan Co., Ltd.
[0803] Softener 2: SYLVARES SA85 manufactured by Arizona Chemical (α-methylstyrene resin (copolymer of α-methylstyrene and styrene), softening point: 85° C.)
[0804] Softener 3: RICON100 manufactured by Sartomer (liquid SBR, styrene content: 20% by mass, vinyl content: 70% by mass, weight average molecular weight: 4500)
[0805] Softener 4: NOVARES C100 manufactured by Rutgers Chemicals (benzofuran indene resin, softening point: 95°C to 105°C)
[0806] Softener 5: Dercolyte L120 manufactured by DRT (polylimonene resin, softening point: 120°C)
[0807] Softener 6: sylvatraxx 4150 manufactured by KRATON (polyterpene resin, softening point: 150°C)
[0808] Silane coupling agent 2: Si266 manufactured by Evonik Degussa
[0809] Silane coupling agent 3: Si69 manufactured by Evonik Degussa
[0810] Silane coupling agent 4: Si363 manufactured by Evonik Degussa
[0811] Anti-aging agent: N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine
[0812] Wax: OZOACE 0355 manufactured by Nippon Seiro Co., Ltd.
[0813] Vulcanization accelerator 1: N-cyclohexyl-2-benzothiazolylsulfenamide
[0814] Vulcanization accelerator 2: diphenylguanidine
[0815]
[0816]
[0817] As shown in Tables 1-1 to 1-5, Tables 2-1 to 2-5, Table 3, Tables 4-1 to 4-4, Tables 5-1 to 5-3, Table 6, Tables 7-1 to 7-2, and Tables 8-1 to 8-2, it was also confirmed that the hydrogenated conjugated diene polymers or hydrogenated conjugated diene polymer compositions of Examples 1 to 30 and Examples 31 to 33 suppressed cold flow compared to Comparative Examples 1 to 15 and Comparative Example 16, and that the Mooney viscosity of the compound when preparing the sulfide was low, showing good processability.
[0818] Furthermore, as shown in Tables 2-1 to 2-5, Table 3, Tables 5-1 to 5-3, Table 6, Tables 7-1 to 7-2, and Tables 8-1 to 8-2, it was confirmed that the rubber compositions of Application Examples 1 to 32 and Application Examples 33 to 54 were superior in breaking strength, breaking elongation, and fracture characteristics after being vulcanized as compared to Application Comparative Examples 1 to 17 and Application Comparative Examples 19 to 24. In particular, from the results of Application Examples 1, 5, 6, 9, 10, 12, 15, 16, and 33, it was confirmed that the balance between strength and fuel efficiency performance was extremely excellent when the hydrogenation rate was in the range of 39% to 80%.
[0819] This application is based on Japanese patent application (Japanese Patent Application No. 2020-068489) filed on April 6, 2020 and Japanese patent application (Japanese Patent Application No. 2020-068479) filed on April 6, 2020, the contents of which are incorporated herein by reference.
[0820] Industrial Applicability
[0821] The hydrogenated conjugated diene polymer of the present invention has industrial applicability as materials for tire treads, automobile interior and exterior products, anti-vibration rubber, conveyor belts, shoes, foams, and various industrial products.
Claims
1. A hydrogenated conjugated diene polymer, in, The degree of branching Bn measured by GPC-light scattering method with a viscosity detector is 2.5 or more, and the hydrogenation rate of the structural unit derived from the conjugated diene compound is 30% or more and less than 60%, or 75% or more and less than 99%.
2. The hydrogenated conjugated diene polymer according to claim 1, in, The weight average molecular weight determined by GPC is 210,000 or more and less than 3,000,000.
3. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, When the constituent ratios of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4) are respectively set to a, b, c, and d, the following mathematical formula (S) is satisfied, wherein the unit of the constituent ratio is mol%. [Chemistry 1] Mathematical formula (S): 20≤(a+b) / (a+b+c+d)×100≤65.
4. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, When the constituent ratios of the structural unit represented by the following formula (1) and the structural unit represented by the following formula (2) are respectively a and b, the following mathematical formula (T) is satisfied, wherein the unit of the constituent ratio is mol%. [Chemistry 2] Mathematical formula (T): 90≤(a) / (a+b)×100≤100. 5 . The hydrogenated conjugated diene polymer according to claim 1 , comprising 3% by mass or more and less than 60% by mass of an aromatic vinyl monomer. 6 . The hydrogenated conjugated diene polymer according to claim 1 , wherein the modification rate is 60% by mass or more.
7. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, The degree of branching Bn measured by GPC-light scattering method with a viscosity detector is 8.0 or more.
8. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, The hydrogenated conjugated diene polymer has a star-shaped polymer structure with three or more branches. A moiety derived from a vinyl monomer containing an alkoxysilyl group or a halosilyl group is present on at least one branch of the star-shaped structure, The portion derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group has a further main chain branch structure.
9. The hydrogenated conjugated diene polymer according to claim 8, in, The portion derived from the vinyl monomer containing an alkoxysilyl group or a halosilyl group is a monomer unit based on a compound represented by the following formula (5) or (6), and having a branching point of the polymer chain caused by a monomer unit based on a compound represented by the following formula (5) or formula (6), At least one end of the hydrogenated conjugated diene polymer is coupled with a coupling agent. [Chemistry 3] In formula (5), R 1 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and a part of the group may have a branched structure; R 2 ~R 3 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of the alkyl group may have a branched structure; When there are multiple R 1 ~R 3 Each is independent; X 1 represents a halogen atom; when there are multiple halogen atoms, X 1 Each is independent; m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3; (m+n+l) represents 3; [Chemistry 4] In formula (6), R 2 ~R 5 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of the alkyl group may have a branched structure; When there are multiple R 2 ~R 5 Each is independent; X 2 ~X 3 Each independently represents a halogen atom; when there are plural X 2 ~X 3 Each is independent; m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3; (m+n+l) represents 3; a represents an integer from 0 to 2, b represents an integer from 0 to 3, c represents an integer from 0 to 3; (a+b+c) represents 3.
10. The hydrogenated conjugated diene polymer according to claim 9, in, The hydrogenated conjugated diene polymer has a monomer unit based on the compound represented by the formula (5), wherein R 1 is a hydrogen atom, m=0.
11. The hydrogenated conjugated diene polymer according to claim 9, in, The hydrogenated conjugated diene polymer has a monomer unit based on a compound represented by the above formula (6), wherein m=0 and b=0.
12. The hydrogenated conjugated diene polymer according to claim 9, in, The hydrogenated conjugated diene polymer has a monomer unit based on the compound represented by the formula (5), wherein R 1 It is a hydrogen atom, m=0, l=0, n=3.
13. The hydrogenated conjugated diene polymer according to claim 9, in, The hydrogenated conjugated diene polymer has a monomer unit based on a compound represented by the formula (6), wherein m=0, l=0, n=3, a=0, b=0, and c=3.
14. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, The component LM, which is a component having a molecular weight of 300,000 or less, accounts for 20% to 80%.
15. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, The hydrogenation rate is 50% or more and 75% or less.
16. The hydrogenated conjugated diene polymer according to claim 5, in, It contains 5 to 40% by mass of an aromatic vinyl monomer.
17. The hydrogenated conjugated diene polymer according to claim 15, in, The degree of branching Bn measured by GPC-light scattering method with a viscosity detector is 30 or less.
18. The hydrogenated conjugated diene polymer according to claim 1 or 2, in, The absolute molecular weight is 28×10 4 Above 2000×10 4 the following.
19. The hydrogenated conjugated diene polymer according to claim 9, in, The coupling agent has a nitrogen atom-containing group, and the hydrogenated conjugated diene polymer contains a nitrogen atom.
20. A method for producing a hydrogenated conjugated diene polymer, comprising the following steps (A) and (E), and further comprising at least one of the following steps (B) and (D), The hydrogenated conjugated diene polymer obtained in step (E) is the hydrogenated conjugated diene polymer according to any one of claims 1 to 19; Step (A): a step of polymerizing a conjugated diene compound alone or polymerizing a conjugated diene compound and an aromatic vinyl compound to obtain a conjugated diene polymer; Step (B): a step of reacting a branching agent with a conjugated diene polymer terminal to obtain a conjugated diene polymer solution containing a branched conjugated diene polymer having an active terminal; Step (D): a step of reacting a coupling agent with the terminal of a conjugated diene polymer; Step (E): a step of subjecting the conjugated diene polymer to a hydrogenation reaction to obtain a hydrogenated conjugated diene polymer. 21 . The method for producing a hydrogenated conjugated diene polymer according to claim 20 , comprising the step (D).
22. The method for producing a hydrogenated conjugated diene polymer according to claim 20 or 21, in, In the step (D), the coupling agent has a nitrogen atom-containing group.
23. The method for producing a hydrogenated conjugated diene polymer according to claim 20 or 21, in, In the step (B), the branching agent is a compound represented by the following formula (5) or (6), In formula (5), R 1 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and a part of the group may have a branched structure; R 2 ~R 3 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of the alkyl group may have a branched structure; When there are multiple R 1 ~R 3 Each is independent; X 1 represents a halogen atom; when there are multiple halogen atoms, X 1 Each is independent; m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3; (m+n+l) represents 3; In formula (6), R 2 ~R 5 Each independently represents an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 20 carbon atoms, and a part of the alkyl group may have a branched structure; When there are multiple R 2 ~R 5 Each is independent; X 2 ~X 3 Each independently represents a halogen atom; when there are plural X 2 ~X 3 Each is independent; m represents an integer from 0 to 2, n represents an integer from 0 to 3, and l represents an integer from 0 to 3; (m+n+l) represents 3; a represents an integer from 0 to 2, b represents an integer from 0 to 3, c represents an integer from 0 to 3; (a+b+c) represents 3.
24. The method for producing a hydrogenated conjugated diene polymer according to claim 23, in, The branching agent is R 1 A compound in which m is a hydrogen atom and m=0.
25. The method for producing a hydrogenated conjugated diene polymer according to claim 23, in, The branching agent is a compound of the formula (6) wherein m=0 and b=0.
26. The method for producing a hydrogenated conjugated diene polymer according to claim 23, in, The branching agent is R 1 A compound wherein m=0, l=0, and n=3 is a hydrogen atom.
27. The method for producing a hydrogenated conjugated diene polymer according to claim 23, in, The branching agent is a compound of formula (6) wherein m=0, l=0, n=3, a=0, b=0, and c=3.
28. The method for producing a hydrogenated conjugated diene polymer according to claim 20 or 21, in, After step (A) and before step (E), the method further comprises: Step (C): a step of further polymerizing a conjugated diene compound alone or polymerizing a conjugated diene compound and an aromatic vinyl compound from a terminal of the conjugated diene polymer to obtain a conjugated diene polymer. 29 . A hydrogenated conjugated diene polymer composition comprising 100 parts by mass of the hydrogenated conjugated diene polymer according to claim 1 and 1 to 60 parts by mass of a rubber softener.
30. A rubber composition comprising a rubber component and 5.0 parts by mass or more and 150 parts by mass or less of a filler relative to 100 parts by mass of the rubber component, The rubber component contains 10 parts by mass or more of the hydrogenated conjugated diene polymer according to any one of claims 1 to 19 or the hydrogenated conjugated diene polymer composition according to claim 29, based on 100 parts by mass of the total amount of the rubber component.
